MPP+ disorders Irg1-Itaconate axis to promote M1 polarization of microglia by activating succinate dehydrogenase - Lin-Yu Wang; Yi-Yun Tang; Wei Zou; Ping Zhang; Xiao-Qing Tang; Ping Zhang (Molecular Biology Reports, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Sex peptide receptor modulates sex pheromone perception plasticity in female Galleria mellonella across mating status - Zhen-Ping Guo; Xu-Dong Pang; Li-Lin Luo; Ming-Qing Yu; Jun-Hong Linghu; Hua-Yan Xie; Guy Smagghe; Tong-Xian Liu; Shun-Hua Gui (Insect Biochemistry and Molecular Biology, 2026)

Vitamin C-engineered lamellar PbI2 framework for efficient and stable FAPbI3 perovskite solar cells - Hao Xiong; Chenzhe Xu; Yixiong Lin; Ping Li; Linqin Jiang; Bo Wu; Baisheng Sa; Yu Qiu (Chemical Engineering Journal, 2026)

Isolation and pathogenicity of Actinobacillus pleuropneumoniae Serovar 19 in pigs - Bo Hong; Guangyuan Yi; XvDong Lin; YingXuan Ye; XiaoLi Liu; Ahmed H. Ghonaim; Yang Zeng; Shuo Zhang; Ping Bai; Wentao Li; Xuexiang Yu; Qigai He (Veterinary Microbiology, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Salinity shapes biofilm community to promote partial nitrification and sulfamethoxazole removal in membrane-aerated biofilm reactors - Zhi-Cheng Wu; Yu-Lin Han; Chen-Wei Zheng; He-Ping Zhao (Journal of Water Process Engineering, 2026)

Analysis of the vibration characteristics of liquid droplets in oil induced by CPG electric field with data-driven assistance - Ye Peng; Yaozhong Hu; Haifeng Gong; Lin Yan; Bao Yu; Hong Yin; Ping Ouyang (Journal of Environmental Chemical Engineering, 2026)

Marsh expansion accelerates mud accumulation on low-energy sandy coasts - Yunwei Wang; Yidong Guo; Xizhao Wang; Hangjie Lin; Yang Yang; Qian Yu; Ya Ping Wang (Geomorphology, 2026)

Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Postbiotics mitigate translucent post-larvae disease (TPD) in Penaeus vannamei by reinforcing hepatopancreatic cytoskeletal integrity against VHVP-2 toxin - Wenqiang Li; Shuang Liu; Jin Yan; Ping Li; Tingting Xu; Jin-Seng Lin; Hsiao-Tung Chang; Ting-Yu Lee; Qingli Zhang (Aquaculture, 2026)

Eccentric compressive performance of CFST columns reinforced with annular stiffeners - Ke-Rong Luo; Bing-Lin Lai; Liang Yu; Bu-Hui Li; Gan-Ping Shu (Engineering Structures, 2026)

Experimental investigation on seismic performance evolution of reinforced concrete columns considering spatially differential corrosion - Yang Liu; Wei-Ping Zhang; Qian-Qian Yu; Hao-Ran Zuo; Xiang-Lin Gu (Engineering Structures, 2026)

Exposure-informed ventilation control for nanoparticle pollutants in an enclosed industrial built environment: A laser metal deposition case study - Ying-Fang Wang; Thi-Cuc Le; Jing Wang; Yu-Tung Dai; Phuong-Uyen Tran; Van-Nghia Tran; Guo-Ping Chang-Chien; Lin-Chi Wang (Building and Environment, 2026)

Weather source heterogeneity affects disease forecasting: A case study of rice bacterial leaf blight in Taiwan - Jie-Hao Ou; Guo-Cih Lin; Yea-Fang Wu; Chi-Yu Chen; Guan-Ying Huang; Hau-Ping Chou; Chien-Chih Kuo; Hsin-Yuh Wu; Qiao-Juan Lai; Chih-Wei Wang; Yi-Chen Tsai; Chang-Hsin Kuo; et al. (Agricultural and Forest Meteorology, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Regional exploitation signals inferred from a data-limited per-recruit assessment of Trichiurus japonicus in Taiwanese waters - Chih-Yu Lin; Yu-Heng Lu; Wen-Qi Xu; Sheng-Ping Wang; Toshihide Kitakado (Regional Studies in Marine Science, 2026)

Anthraquinone‑modulated oxygen disproportionation enables highly selective singlet oxygen generation for pollutant degradation - Yu Luo; Chenqi Lu; Chuang Xiao; Lin Ding; Mengyuan Zhao; Lingling Liu; Longshuai Zhang; Xibao Li; Fang Deng; Xubiao Luo; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Limonene-loaded nanostructured lipid carriers incorporated in hydrogels: Enhanced acid stability and controlled release properties” [Food Res. Int. 214 (2025) 116601] - Simin Feng; Yitong Tian; Jiahao Yu; Yang Lin; Alan Giovanini de Oliveira Sartori; Ping Shao (Food Research International, 2026)

Unraveling the impact of food processing technologies on postbiotic bioactivity, food matrix interactions, and human health outcomes - Junxin Zhao; Mengfei Duan; Ruiying Xu; Yumeng Cheng; Jinheng Li; Deguo Wang; Xianghui Yan; Ping Yu; Zheling Zeng; Yunzhi Lin; Yoshimitsu Masuda; Ken-ichi Honjoh; et al. (Food Bioscience, 2026)

Non-overtly damaging cold atmospheric plasma induces adaptive epidermal molecular responses associated with integrin alpha 6 - Yu-Ping Cheng; Hua-Lin Chen; Yu-Hsuan Chen; Chang-Sheng Chen; Kuan-Wei Lee; Jong-Shinn Wu; Yun-Chien Cheng; Shih-Chang Lin; Jiun-Wen Guo (Chemico-Biological Interactions, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Topical delivery of Lidocaine using spicules for local anesthesia - Chi Zhang; Ping Yang; Xueke Lin; Huijung Lai; Yi Liu; Shifeng Yu; Tszyam Liu; Ming Chen; Yongxiang Huang (Drug Delivery and Translational Research, 2026)

Integrating slush samples and eDNA metabarcoding to enhance marine fish biodiversity monitoring - Qilin Gutang; Hancheng Zhao; Xiaoxuan Yu; Yan Gao; Kunhuan Li; Jianghua Yang; Xiaowei Zhang; Ping Li; Edmond Sanganyado; Zonghang Zhang; Jianqing Lin; Wenhua Liu (Fisheries Research, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Automated computer vision monitoring of black soldier fly larval growth using metaheuristic optimization for waste-to-feed bioconversion - Jui-Sheng Chou; Benjawan Phakdee; Zih-Tong Lin; Chang-Ping Yu; Pei-Hsun Wu; Cheng-jen Shih (Computers and Electronics in Agriculture, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Corrigendum to “OsCOPT7 is involved in copper accumulation and transport through xylem” [J Hazard Mater 477 (2024) 135245] - Mei Yan Guan; Zhenzhen Cao; Yu Chun Xia; Ping Xv; Xiao Yan Lin; Ming Xue Chen (Journal of Hazardous Materials, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Green synthesized Cu2O/TiO2 nanotube heterojunction for pharmaceutical mineralization and simultaneous hydrogen evolution: mechanistic insight and toxicity assessment - Fang-Yu Liang; Dong-Ni Wu; Wan-Chun Lin; Yi-Ching Lin; Chia-En Tsai; Chia-Hua Lin; Wu-Xing Chen; Chia-Hung Chen; Yen-Ping Peng (Journal of Environmental Management, 2026)

Southern Asian arc magmatism drove Eocene global climate - Xiaoran Zhang; Shuiyue Xue; Sun-Lin Chung; Guochun Zhao; Yu-Ming Lai; Hao-Yang Lee; Ping-Ping Liu (Global and Planetary Change, 2026)

A promising approach for developing functional gummies with enhanced extraction and stability of anthocyanins using β-cyclodextrin-based natural deep eutectic solvents - Jiahao Yu; Mengqiu Xu; Yang Lin; Yong Cheng; Ping Shao (Food Research International, 2026)

Green and sustainable dual-pathway strategies for high-efficiency photoconversion of ergosterol to vitamin D₂ from agaricus bisporus - Jiahao Yu; Yan Tang; Yang Lin; Simin Feng; Mofei Shen; Ping Shao (Food Chemistry, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Mechanically engineered multi-oxide heterojunctions for bifunctional antibacterial and photocatalytic environmental remediation - Juan Pei; Jialan Mi; Shuhan Yao; Mingxing Guo; Ye Zhang; Xiaoling Wan; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Haichun Zeng; et al. (Journal of Environmental Chemical Engineering, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Different land use types around megacities contribute contrasting heavy metal pollution and health risks in soil-leaf vegetable systems - Ling Huang; Wen-Fei Chen; Yue-E Guan; Yan-Ping Pang; Sheng-Gong Yu; Lin Li; Qi Zou; Meng-Qiang Sun; Hang Wei; Zhi-Liang Chen (Environmental Research, 2026)

Acupuncture improves neurological function in ICH rats via suppression of WNK-SPAK-NKCC1 signaling activation - Bai-Wen Zhang; Lei Zheng; Bing-Lin Kuang; Jia Zheng; Xue-Ping Yu; Xiao-Hong Dai; Wei Zou (Journal of Molecular Histology, 2026)

The aging eye: navigating molecular mechanisms and innovative interventions - Yumeng Lin; Zhongyu Han; Yunfeng Zhang; Ruimin Yuan; Mingyu Huang; Yating Liu; Jun Wang; Chen Xu; Luze Liu; Ping Yu; Qingsong Yang; Liuzhi Zeng; et al. (Biogerontology, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Characteristics of structural superimposed halo at the Jiawula Ag-Pb-Zn deposit, Inner Mongolia, China and its significance for exploration - Xin-yu Gao; Gui-yuan Sun; Kang Wang; Wei Zhang; Zhi-ping Li; Wen-ju Li; Jiang Wei; Lin Yang; Hong-zhe Xie; Zi-wen Yang; Chao Ma (Journal of Geochemical Exploration, 2026)

A new Rhizomucor miehei lipase immobilized on anhydride-hydrophobized amino supports: Optimization, characterization and application in preparing medium- and long-chain structured lipids - Yiyi Lin; Xiansi Gao; Zheling Zeng; Di Kuang; Kai Fang; Tianyi Song; Ping Yu; Deming Gong; Cheng Zeng; Xianghui Yan (Food Bioscience, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Dehydroepiandrosterone activates ADGRG2 to regulate chloride homeostasis and sperm motility via Gs-cAMP pathways - Dan Jiang; Ji-Fei Han; Xian-Zheng Guo; Yu-Qi Ping; Fan Yang; Peng Xiao; Jin-Peng Sun; Xiao Yu; Zhao Yang; Hui Lin (Science China Life Sciences, 2026)

Applying the iRIC Morpho2DH model to determine the effectiveness of check dams against debris flows - Zheng-Yi Feng; Philipp Marr; Tien-Chun Hsu; Ping-Hsuan Kuo; Yu-Po Lin; Ming-Chih Chuang; Ching-Mao Huang; Edoardo Carraro; Su-Chin Chen; Chen-Yu Chen; Thomas Glade (Landslides, 2026)

Targeting aryl hydrocarbon receptor signaling attenuates hypertension programmed by maternal Di-2-ethylhexylphthalate exposure - Chien-Ning Hsu; Hsi-Yun Liu; Chih-Yao Hou; Yu-Wei Chen; Guo-Ping Chang-Chien; Shu-Fen Lin; You-Lin Tain (Toxicology and Applied Pharmacology, 2026)

Microbial N2O production and the functional communities regulated by groundwater flow regime - Yaqi Wang; Helin Wang; Lin Zhang; Yu Han; Ping Li; Yanxin Wang (Journal of Hydrology, 2026)

High-throughput fingerprinting of hydrolysable tannins in wine and oak wood using in-source fragmentation on QTOF and QQQ platforms - Yanxin Lin; Bruce S. Pan; Robert (Qiang) Sui; Ping Yu; Misha T. Kwasniewski (Food Chemistry, 2026)

Thin film nanocomposite membrane incorporated with sulfonic acid-based HOFs for efficient reverse osmosis desalination - Yu-ting Liu; Zi-yue Tang; Zi-ao Zong; Wan-zhen Wang; Xiao-yin Zhang; Xin-ping Song; Xiang-min Meng; Rijia Lin; Jingwei Hou (Desalination, 2026)

USP7 protects histone H1.2 from proteasome-mediated degradation to facilitate DNA repair and pancreatic neuroendocrine neoplasms progression - Mujie Ye; Lin Xu; Ping Yu; Jialing Pan; Xiaoting Shi; Bingyan Xue; Na He; Ping Hu; Min Liu; Xintong Lu; Yuemei Xu; Yanling Xu; et al. (Science China Life Sciences, 2026)

Unraveling iron and zinc efficiency in pepper: integration of root architecture, uptake kinetics, and transcriptional regulation - Cheng-Xiang Zhou; Wei Zhang; Bao-Gang Yu; Hao-Feng Yang; Yuan Wang; Kai Sun; Fu-Lin Zhao; Huai-Yu Yang; Prakash Lakshmanan; Xin-Ping Chen; Chun-Qin Zou (Plant and Soil, 2026)

The presence of native semi-fossorial herbivores enhances the coupling between species and functional diversity in alpine meadows - Yuan Yuan Duan; Kun Qin; Yu Chen; Jie Li; Ni Wang; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Agriculture, Ecosystems & Environment, 2026)

Spatio-temporal dynamics for dolphinfish (Coryphaena hippurus) in the waters around Taiwan: Implications for stock assessment and fisheries management - Wen-Qi Xu; Sheng-Ping Wang; Chih-Yu Lin; Wei-Chuan Chiang; Toshihide Kitakado (Regional Studies in Marine Science, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Effect of protein–polyphenol interactions on the structural and digestive properties of pork myofibrillar proteins - Yu Chen; Qingyao Jiang; Yan Lu; Qiao Zeng; Ping Liu; Jiaxin Chen; Hongbin Lin; Jie Tang; Jie Zhao (Journal of Food Engineering, 2026)

In-situ reactivation of the catalyst for hydrodeoxygenation of bio-oil to biofuel by coupling the self-rotation and revolution of catalysts in the swirling flow - Yao Zhang; Zheng-hao Yang; Yu-long Chang; Jian-ping Li; Bang-da Wang; Zi-heng Jin; Liang Ma; Xia Jiang; Hua-lin Wang (Journal of Cleaner Production, 2026)

Self-cleaning nanofiber membrane for efficient oil-water separation and dye degradation - Hai-chao Bai; Zi-yue Tang; Zi-ao Zong; Xin-ping Song; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Rijia Lin; Jingwei Hou (Journal of Cleaner Production, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

Correction: Modulation of the immune response by focused ultrasound suppressed brain abscess formation - Zhuo-Hao Liu; Nan-Yu Chen; Chiung-Yin Huang; Ya-Jui Lin; Ping K. Yip; Kuo-Chen Wei; Hao-Li Liu (Drug Delivery and Translational Research, 2026)

Modulation of the immune response by focused ultrasound suppressed brain abscess formation - Zhuo-Hao Liu; Nan-Yu Chen; Chiung-Yin Huang; Ya-Jui Lin; Ping K. Yip; Kuo-Chen Wei; Hao-Li Liu (Drug Delivery and Translational Research, 2026)

On-exosome-membrane DNA polymerization-powered magneto-electrochemical aptasensing for osteosarcoma - Guang-Xian Zhong; Huang-Feng Lin; Fei-Huan Fu; Jing-Wei Zhou; Chong-Yu Chen; Chao-Yang Wu; Jian-Ping Lin; Xiong-Wei Xu; Jian-Hua Lin; Jin-Yuan Chen (Analytica Chimica Acta, 2026)

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

Toward sustainable use of dolphinfish (Coryphaena hippurus) in the Northwest Pacific: A framework for stock assessment and management strategy evaluation - Sheng-Ping Wang; Wen-Qi Xu; Chih-Yu Lin; Toshihide Kitakado; Wei-Chuan Chiang (Regional Studies in Marine Science, 2026)

Enhanced fluoxetine removal from water via Fe/Cu-doped biochar-activated percarbonate under sunlight and aeration - Yang Wu; Zhi-hao Li; Xi-xi Lu; Zi-xuan Lin; Chang-ping Yu (Journal of Environmental Chemical Engineering, 2026)

Identification, antioxidant and acetylcholinesterase inhibitory activities of soluble and insoluble-bioactive components from Cinnamomum camphora seed kernel residue - Pinpin Zhang; Junmin Long; Zheling Zeng; Xianghui Yan; Yujing Yang; Rongping Fu; Yuling Lin; Deming Gong; Cheng Zeng; Ping Yu (Food Research International, 2026)

Aqueous LC-MS/MS quantification of α-/β-nicotinamide mononucleotide in dietary supplements using a pentabromophenyl column - Chng Sze Hoei; Nian-Hua Wu; Chao-Ming Tsen; Ping-Wei Sun; Han-Wei Chang; Shin-Yuan Wang; Hung-Yu Lin (Analytica Chimica Acta, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Caffeoylquinic acid derivatives (CQAs) from Daphne gemmata and their antimicrobial activities - Lin Li; Fu-Qiang Song; Ping-Jing Yu; Li-Ping Tang; Xian Li (Natural Product Research, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Corrigendum to “Cluster-based identification of fishing strategies with robustness assessment: A case study of Taiwanese albacore longline fisheries in the Indian Ocean” [Reg. Stud. Mar. Sci. 93 (2026) 104713] - Sheng-Ping Wang; Sung-Il Lee; Wen-Qi Xu; Chih-Yu Lin; Wen-Pei Tsai; Toshihide Kitakado (Regional Studies in Marine Science, 2026)

Cluster-based identification of fishing strategies with robustness assessment: A case study of Taiwanese albacore longline fisheries in the Indian Ocean - Sheng-Ping Wang; Sung-Il Lee; Wen-Qi Xu; Chih-Yu Lin; Wen-Pei Tsai; Toshihide Kitakado (Regional Studies in Marine Science, 2026)

Unveiling the interaction of uranyl and arsenate: Insights into the formation mechanisms of uranyl arsenate minerals - Penggang Li; Ping Zhang; Zhihui Yang; Lin Yu; Junhao Zheng; Mengying Si; Qi Liao; Feiping Zhao; Weichun Yang (Journal of Environmental Sciences, 2026)

Seasonal modulation of the spring-neap response of Yangtze Estuary turbidity maximum: Movement, amplitude, and phase lag via remote sensing - Jie Feng; Qian Yu; Shiyi Cao; Zhiyun Du; Hangjie Lin; Ya Ping Wang; Yunwei Wang (Estuarine, Coastal and Shelf Science, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Statistical characteristics of storm cells and centroid-based probability nowcasts by tracking error - Kao-Shen Chung; Tsai-Jung Lee; Li-Pen Wang; Bing-Zhang Wang; Chieh-Ying Ke; Yi-Hao Tsou; Shin-Gan Chen; Ping-Yu Lin; Treng-Shi Huang (Atmospheric Research, 2026)

A proposed framework based on traffic volume and the design of a bottom-up methodology to estimate the CO emission of on-road vehicles - Shan-Yi Shen; Ru-Yun Chang; Yun-Wei Liao; Wei-Chun Chou; Yu-Hao Lin; Ping-Yu Liu (Atmospheric Pollution Research, 2026)

Analysis of clinical characteristics and prognostic factors in AIDS complicated by cryptococcal meningitis - Yanlan Liang; Xiyang Dong; Yong Deng; Zhende Lin; Caixia Zheng; Jiaxuan Li; Yijie Lin; Huatang Zhang; Xing Wang; Wenwu Lin; Wencong Hong; Su Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Predictions about the hourly effluents in the real anaerobic-oxic wastewater treatment process made by the optimized bidirectional long short-term memory network - Yu-Hao Lin; Hung-Hsiao Hsu; Ping-Yu Liu (Journal of Water Process Engineering, 2025)

Stable isotopes reveal the evaporation effects during a drought–flood abrupt alternation period in a semiarid river basin in Inner Mongolia, Northwest China - Jian Luo; Chengcheng Xia; Guoqing Wang; Ruihong Yu; Ruizhong Gao; Xiaomin Liu; Ping Miao; Qiuyu Qiao; Junxi Lin (Journal of Hydrology, 2025)

A refined calibration of the Na-Li geothermometer for pelitic lithologies before and after orogenic metamorphism - Hou-Chun Liu; Chao-Chang Chen; Yi-Chia Lu; Huai-Jen Yang; Yan-Hong Chen; Yu-Feng Lu; In-Tian Lin; Sung-Ping Chang (Geothermics, 2025)

Revealing the polyphenol modulation mechanism for in vitro gastric digestion properties of myofibrillar proteins via noncovalent interaction - Yan Lu; Chaoqun Chen; Yu Chen; Shuaiqian Wang; Yanping Hu; Ping Liu; Hongbin Lin; Jie Tang; Jie Zhao (Food Chemistry, 2025)

LPS disrupts erythroid-myeloid balance in zebrafish via Jak2/Stat3-Hif1a signaling - Hai-Chuan Yu; Meng-Yao Chen; Shuang-Ling Zhang; Fang-Chao Tong; Fan-Ping Wang; Lin Wang; Jia-Long Zhang; Jiao-Jie Guo; Bing-Yang Zhang; Jia-Qi Tian; Jiao Wu (Fish & Shellfish Immunology, 2025)

In-situ control of biohythane production in electro-anaerobic digestion - Chao-Chin Chang; Yu-Wen Lin; Chang-Ping Yu; Zhen He (Chemical Engineering Journal, 2025)

Unveiling the role of Zn−N1S3 sites in atomic-precision ZnIn2S4/g-C3N4 heterostructure for highly efficient CO2-to-CO conversion - Hossam A.E. Omr; Raghunath Putikam; Mahmoud Kamal Hussien; Amr Sabbah; Tsai-Yu Lin; Kuei-Hsien Chen; Li-Chyong Chen; Heng-Liang Wu; Shien-Ping Feng; Ming-Chang Lin; Hyeonseok Lee (Chemical Engineering Journal, 2025)

Correction: Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2025)

Multiple Mechanisms and Therapeutic Strategies for the Involvement of AMPK in the Development of Alzheimer’s Disease - Lin Yu; Xue Yang; Hui-Ping Lei; Yue-Ting Hu; Ling-Nan Wu; Shao-Yu Zhou; Feng Jin (Molecular Neurobiology, 2025)

Inverse Admittance Characteristics of Gastric Cancer Cells Measured by a Validated Dielectrophoretic Microfluidic Platform - Jia‑Jiun Tsai; Yun-Jung Tsai; Mei Yu Huang; Chun-Ping Jen; Shu-Hui Lin (Journal of Medical and Biological Engineering, 2025)

Effects of MS-222 on the physiological and biochemical response, histomorphology, gut microbiota, and flesh quality in largemouth bass (Micropterus salmoides) - Ping Gao; Rimeng Chen; ShanShan Lin; Haodong Yu; Xuezhen Zhang (Fish Physiology and Biochemistry, 2025)

Spatio-temporal heterogeneity of the estuarine turbidity maximum retreat in the Changjiang river estuary under reduced sediment supply - Jie Feng; Qian Yu; Shiyi Cao; Shiyu Zhang; Tianxu Ni; Zhiyun Du; Hangjie Lin; Yunwei Wang; Ya Ping Wang (Geo-Marine Letters, 2025)

Using an acidic vesicle tracer to identify potential bacterivores in coastal waters of the subtropical Western Pacific Ocean - Yun-Chi Lin; Yu-Chen Lin; Kuo-Ping Chiang; Chien-Pang Chin; Wen-Chen Chou (Frontiers in Marine Science, 2025)
Bacterivores play a key role in transferring energy through microbial food webs and are broadly classified as heterotrophic or mixotrophic based on the presence of inherent chloroplasts. Mixotrophs, especially in low-latitude regions, have recently gained attention due to their dual roles as primary producers and bacterial grazers, which enable them to thrive in nutrient-poor, stratified waters where traditional autotrophs or heterotrophs may be less competitive. This study investigated the composition of bacterivores in the coastal waters of northeastern Taiwan during the warm season (July and August 2022). A combination of LysoTracker staining, flow cytometry sorting, and 18S rRNA gene amplicon sequencing was used to rapidly identify heterotrophic and mixotrophic nanoflagellates (HNFs and MNFs, respectively) based on chloroplast autofluorescence. The dominant eukaryotic lineages included Alveolata, Stramenopiles, Opisthokonta, Chlorophyta, and Rhizaria. HNFs were primarily composed of MAST clades, choanoflagellates (Opisthokonta), Telonemia, and Radiolaria, while MNFs included cryptophytes, haptophytes, and chlorophytes such as Mamiella , Mantoniella and Tetraselmis , as well as stramenopiles like Dictyochophyceae and Chrysophyceae. Notably, several non-motile chlorophytes, including Chloropicon and members of Pycnococcaceae, were identified as potential bacterivores based on Lysotracker signals; however, their phagotrophic capability requires further confirmation in future studies. Despite the limitations of LysoTracker-based methods, this study reveals previously overlooked mixotrophic diversity and highlights the need for further validation. These findings advance our understanding of carbon flow and microbial dynamics in subtropical marine ecosystems under changing environmental conditions.

Real-world emissions and total output from fishing vessels in Taiwan - Po-Yen Chien; Chia-Hsiang Lai; Wu-Xing Chen; Chia-Hung Chen; Chia C. Wang; Amila Kasun Abeysinghe; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Yu-Lun Tseng; Pei-Shih Chen; Yen-Ping Peng (Transportation Research Part D: Transport and Environment, 2025)

The influence of trees shade level on human thermal comfort and the development of applied assessment tools - Yu-Ying Wei; Ching-Yin Cheng; Tzu-Ping Lin (Landscape and Urban Planning, 2025)

Effects of aeration gradient on simultaneous nitrification and denitrification in MABR under low nutrient concentrations: Experimental and modeling investigation - Gong-Hao Zhao; Yu-Lin Han; Chun-Yu Lai; He-Ping Zhao (Journal of Water Process Engineering, 2025)

Naringenin-loaded Flammulina velutipes chitin-glucan complexes gel system: structural modulation and dual lipid-lowering mechanisms - Simin Feng; Shuqi Liang; Jianyu Yang; Jiahao Yu; Yang Lin; Yizhen Xie; Peilong Sun; Ping Shao (Food Chemistry, 2025)

Mechanochemical synthesis of ZnO@TiO2 II heterojunction material: Photocatalytic degradation and antibacterial synergistic effect - Juan Pei; Xiaoling Wan; Mingxing Guo; Jialan Mi; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Siwei Xiang; Qianyu Zhang; Haichun Zeng; et al. (Chemical Engineering Journal, 2025)

Elucidating the suppressive role of native bacterial traits against root-knot nematodes to control plant-parasitic effect in serpentine hostile rhizosphere soil - Aslia Asif; Liang-Yu Lin; Ping-Chi Hsu; Suprokash Koner; Zeng-Yei Hseu; Tsui-Kang Hsu; Shih-Wei Huang; Bing-Mu Hsu (Applied Soil Ecology, 2025)

Estimating and classifying urban carbon budget based on land use intensity with regulatory strategies developing - Li-tzu Yu; Cing Chang; Tzu-Ping Lin (Sustainable Cities and Society, 2025)

Chemical constituents isolated from leaves of seashore plant Aglaia rimosa - Jing-Ru Weng; Jui-Hsin Su; Ping-Jyun Sung; Wei-Yu Lin; Zhen-Hong Han; You-Ying Chen; Chun-Lin Chen (Phytochemistry Letters, 2025)

Corrigendum to ‘Isolation of undescribed cladosporols and spirobisnaphthalenes from a plant pathogen Cladosporium cladosporioides F-10-2-A’ [Phytochemistry. 222 (2024) 114073] - Peng Li; Zi Jin Zhang; Yu Tong Guo; Jing Guan; Lin Bo Wen Xi; Li Ping Lin (Phytochemistry, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Upregulation of PD-1 on Peripheral T cells Subsets is Associated with Parkinson's Disease - Zhi-Ling Zhang; Pang-Hai Ye; Wei-Xin Kong; Jin Li; Si Zhu; Yu-Wan Lin; Ping-Yi Xu; Wen-Yuan Guo (Molecular Neurobiology, 2025)

Molecular screening of wild and cultivated tomato germplasm reveals potential materials for multi-locus disease resistance breeding - Ehtisham Hussain; Chien-yu Cheng; I-min Huang; Chen-yu Lin; Samrin Gul; Ijaz Rasool Noorka; Assaf Eybishitz; Chutchamas Kanchana-udomkan; Maarten van Zonneveld; Ya-ping Lin (Genetic Resources and Crop Evolution, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Integrating machine learning and metabolomics to uncover new biomarkers for predicting pesticide exposure among patients with kidney function decline - Junne-Ming Sung; Yu-Chi Hung; Wan-Ru Wang; Chiau-Jun Chu; Yen-Ping Lin; Kuan-Hung Liu; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Elucidating the photodesorption mechanism of sulfamethoxazole on novel photo-responsive copper-phenylacetylide: Cleavage of π-π interactions and Cu O bonds - Rong Chen; Zhenjun Xiao; Zili Lin; Yishun Wang; Yu Chen; Ping Chen; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2025)

Photothermally responsive conductive hydrogels for dual-mode self-sensing soft actuators - Chengnan Qian; Ping Guo; Ruofei Wang; Xuanzi Luo; Yang Yu; Lin Cheng; Aiping Liu (Chemical Engineering Journal, 2025)

Self-cleaning nanofiber membranes for sustainable dual removal of oils and dyes from wastewater - Hai-chao Bai; Yu-kun Sun; Zi-yue Tang; Zi-ao Zong; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Jingwei Hou; Rijia Lin (Chemical Engineering Journal, 2025)

Field Tests Using High-Power Microwaves to Crack Iron Ore of Different Grades - Feng Lin; Xia-Ting Feng; Shi-Ping Li; Tian-Yang Tong; Yun-Tan Ao; Yu-Xi Liu (Rock Mechanics and Rock Engineering, 2025)

Chinese Tuina ameliorates muscle damage by regulating endoplasmic reticulum stress and autophagy in a rat model of skeletal muscle contusion - Hai-chao Liu; Hao-ming Zhu; Ming Li; Bo-rui Chen; Zheng-yu Yang; Yu Wang; Shi-zhong Wang; Shao-qing Chen; Jian-ping Lin (Tissue and Cell, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A PLA2-responsive nanoagonist to boost immunotherapy via targeted release of lipid mediators in cold tumor microenvironment - Hui-Ping Wen; Meng-Die Zhu; Di Ning; Zhi-Gang Wang; Yusi Hu; Chuan-Ming Yu; Dai-Wen Pang; Shu-Lin Liu (Science Bulletin, 2025)

Harnessing AI and advanced modeling for precision ozone control: A data-driven approach to air quality management - Guan-Yu Lin; Jih-Wen Zheng; Yen-Ping Peng; Gung-Hwa Hong (Journal of Hazardous Materials, 2025)

Seasonal characteristics, source apportionment and ecological risk assessment of priority and emerging contaminants using passive samplers in the coastal water - Zishan Diao; Xianyin Ping; Xue Zhang; Bin Hui; Fanping Zhu; Yiqiao Zhang; Jing Wang; Yinjie Yu; Lin Zhang; Wenjia Hui; Xiaomin Xie; Xiaohan Zhang; et al. (Journal of Hazardous Materials, 2025)

Limonene-loaded nanostructured lipid carriers incorporated in hydrogels: Enhanced acid stability and controlled release properties - Simin Feng; Yitong Tian; Jiahao Yu; Yang Lin; Alan Giovanini de Oliveira Sartori; Ping Shao (Food Research International, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

An intelligent flame detection and information acquisition method for early fires: Achieving real-time fire spatial localization and dimension measurement - Xiajun Lin; Longxing Yu; Chunxiang Liu; Zhi Hong; Peiling Zhang; Ping Huang (Process Safety and Environmental Protection, 2025)

A modeling framework for assessing the future changes in the occurrence of extreme rain-induced landslides - Xinlong Zhang; Qigen Lin; Manhoi Lok; Taosheng Huang; Xuan Yu; Weiping Wang; Ping Shen (Gondwana Research, 2025)

Dynamics of Suspended Sediment Variability Over Various Timescales: A Quantitative Analysis Using Remote Sensing Data - Zhiyun Du; Hangjie Lin; Qian Yu; Yunwei Wang; Yun Peng; Li Wang; Shu Gao; Ya Ping Wang (Estuaries and Coasts, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Geothermal gas geochemistry in Southeast Tibetan Plateau margin influenced by magma chambers and fractures - Jia-Yi Wu; Hai Gang Cao; Peng Cheng Zhao; Yu Ping Guo; Xue-Gang Chen; Xiaohu Li; Jui-Fen Tsai; Pei-Ling Wang; Li-Hung Lin (Journal of Volcanology and Geothermal Research, 2025)

The influence of shading facilities on outdoor thermal comfort, pedestrian walking speed, and indoor satisfaction - Zi-En Lin; Shiang-Yu Wang; Kuo-An Hung; Chiao-Jou Hsieh; Tzu-Ping Lin (International Journal of Biometeorology, 2025)

3D printed microtissue cassettes enabling high throughput proton radiobiological assays - Chih-Tsung Yang; I-Chun Cho; Ching-Fang Yu; Edward Cheah; Tesi Liu; Yi-Ping Lin; Sing-Yu Hu; Jyun-Wei Jheng; Ivan Kempson; Tsi-Chian Chao; Sen-Hao Lee; Eva Bezak; et al. (Analytica Chimica Acta, 2025)

Five undescribed chromone-phenylpyridone hybrids from Cineraria repanda-derived Penicillium oxalicum with cytotoxic and antibacterial activity - Yu Wei Huang; Jing Guan; Yin Tang; Ren Xiang Tan; Li Ping Lin (Phytochemistry, 2025)

Development of an alkali-producing bioelectrochemical system for sewage-polluted seawater: nutrient removal, scalant mitigation, and resource recovery - Chao-Chin Chang; Chieh-Yun Wu; Jia-Zhe Jiang; Chen-An Hsu; Chang-Ping Yu; Yi-Li Lin (Journal of Water Process Engineering, 2025)

The enhanced Huyou (Citrus changshanensis) segment peeling of ultrasound combined with pectinase and cellulase is reflected on the sonicated segment rather than enzymes - Yang Lin; Zhaoqi Yu; Lixia Wang; Xiaozhong Xu; Shixiang Xu; Ping Shao (Innovative Food Science & Emerging Technologies, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Pepper feeding derivative Brucella sp. in the gut of Spodoptera litura (Lepidoptera: Noctuidae) affect the growth and development of host larvae - Yu Wang; Zhou Yu; Bei-Long Chen; Shao-Shao He; Zi-Yao Liu; Zheng Zhai; Lin Chen; Jiang-Bin Fan; Huan Yu; Zhi-Ping Zuo; Yong-Sheng Zhang (Pesticide Biochemistry and Physiology, 2025)

Junceellolide Q, a new polyacetoxybriarane from the delicate sea whip octocoral Junceella fragilis - Yih-Gang Goan; Mingzi M. Zhang; Lun Kelvin Tsou; Zhi-Hong Wen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yu-Jen Wu; Jih-Jung Chen; Hai Nhat Do; Pei-Luen Jiang; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Cooperation of Lactoplantibacillus plantarum and polyethylene microplastics facilitated the disappearance of tetracycline during anaerobic fermentation of whole plant maize - Yubo Zhang; Pan Wang; Yu Tang; Chaosheng Liao; Xiaolong Tang; Pai Hou; Cheng Chen; Xiaokang Huang; Guangrou Lu; Lin Li; Mingjie Zhang; Fuxiang Li; et al. (Journal of Hazardous Materials, 2025)

Metallization-mediated charge transfer in cocrystals for efficient photocatalytic decontamination of mustard-gas simulant - Li Zhang; Xiao-Lin Liu; Chen Sun; Yu-Ting Luo; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2025)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

Polyploid crape myrtle was produced through hybridizing with 2n gametes induced by high-temperature - Yu Xu; Qi Hu; Qifang Lin; Xiufeng Chi; Ping Shen; Xin Wang; Zhiting Wan; Xinwei Jiang; Jia Wang; Tangren Cheng; Qixiang Zhang; Huitang Pan (Euphytica, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Aflatoxin B1 exposure induces Alzheimer's disease like pathology by disrupting redox homeostasis and activating ferroptotic signals in C57BL/6 J mice - Jinxian Lin; Huihui Hong; Sicheng Liu; Zhengwei Liang; Qixue Zheng; Kun Luo; Jiayi Li; Zhulin Du; Jinping Yu; Lingling Yang; Ping Deng; Huifeng Pi; et al. (Science of The Total Environment, 2025)

Inhibitory effect of organometallic framework composite nanomaterial ZIF8@ZIF67 on different pathogenic microorganisms of silkworms - Zhen-Yu Shen; Samreen Sadiq; Tao Xu; Ping Wu; Iltaf Khan; Xinhao Jiao; Aftab Khan; Lulai Wang; Su Lin (Pesticide Biochemistry and Physiology, 2025)

Five brasilane-type sesquiterpenoids with neuroprotective activities from Xylaria nigripes - Hong-Ping Long; Xi Zhou; Si-Qian Zhou; Lan-Qing Li; Ai-Lin Liang; Wen-Yu Lu; Wen-Xuan Wang; Shao Liu; Jing Li; Ji-Kai Liu (Phytochemistry, 2025)

Interpretation of machine learning-based prediction models and functional metagenomic approach to identify critical genes in HBCD degradation - Yu-Jie Lin; Ping-Heng Hsieh; Chun-Chia Mao; Yang-Hsin Shih; Shu-Hwa Chen; Chung-Yen Lin (Journal of Hazardous Materials, 2025)

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Hydrogel-filled micropipette enables antifouling in vivo iontronic sensing - Guangguo Guo; Yifei Pan; Tianyi Xiong; Wenliang Ji; Wenjie Ma; Ping Yu; Yuqing Lin; Lanqun Mao (Science Bulletin, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Antimicrobial efficacy of carvacrol-loaded curdlan hydrogels for enhancing shelf-life in seafood packaging applications - Hong-Ting Victor Lin; Yi-Chi Yu; Shu-Han Yu; Yu-Chieh Chou; Hsuan-Ju Lin; Shella Permatasari Santoso; Shin-Ping Lin (International Journal of Food Microbiology, 2025)

Synergistic effects of accompanying heterotrophic bacteria on sulfide-based autotrophic denitrification - Yu-Lin Han; Zhen-Chuan Wu; Feng Jiang; He-Ping Zhao (Chemical Engineering Journal, 2025)

Chronic polyaluminum chloride perturbation shaped community assembly patterns: An overlooked mechanism of nitrogen removal inhibition - Nan-ping Wu; Qian Zhang; Hong-yu Wang; Yun-jie Zhang; Meng Li; Bin Ji; Yufei Bao; Bing Lin; Yu-wei Ding; Qi He; Jia-jing Chen (Chemical Engineering Journal, 2025)

Achieving efficient autotrophic nitrogen removal in anaerobic membrane bioreactor plus membrane aerated biofilm reactor by regulating nutrient ratios - Yu-Lin Han; Ling-Dong Shi; He-Ping Zhao (Bioresource Technology, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Combining geographic information and climate data to develop urban building energy prediction models in Taichung, Taiwan - Cing Chang; Chieh-Yu Chen; Tzu-Ping Lin (Sustainable Cities and Society, 2024)

Regulation of freshwater filamentous green algae (Cladophora) and its impact on malodorous volatile organic sulfur compound (DMS) by biomanipulation - Yutai Dai; Yu Lin; Ping Deng; Jiping Chen; Weijie Li; Qiang Gao; Hong Shen; Qiutong Peng; Mo Chen; Xuwei Deng (Science of The Total Environment, 2024)

Integration of automatic discontinuity identification and multi-scale hierarchical modeling for stability analysis of highly-jointed rock slopes - Ya-ping Wang; Jia-wen Zhou; Jun-lin Chen; Yu-chuan Yang; Fei Ye; Hai-bo Li (International Journal of Rock Mechanics and Mining Sciences, 2024)

Molecular properties, structure, neurotrophic and anti-inflammatory activities of cultured secondary metabolites from the cultures of the mushroom Cyathus striatus CBPFE A06 - Jing Wei; Mei-Yu Ye; Zhen-Xin Wang; Yi-Lin Zhang; Xuan-Sheng Hu; He-ping Hui; Yi-tong Liu; Jianzhao Qi (Natural Product Research, 2024)

Analysis of chemosensitivity of tumor spheroids exposed to two-dimensional gradient of combination drugs in a hydrogel-based diffusion microfluidic platform - Kin Fong Lei; Yu-Ting Lin; Sai Kiran Reddy Boreddy; Ping-Ching Pai (Analytica Chimica Acta, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

A wearable exhaled breath condensate (EBC) collector with controllable condensation microfluidics and a branched hydrophilic film - Chun-Hao Chang; Ying-Hsuan Yu; Hsiu-Pen Lin; Ping-Hsien Tsou; Yaw-Kuen Li; Bor-Ran Li (Chemical Engineering Journal, 2024)

Prim-O-glucosylcimifugin alleviates influenza virus-induced pneumonia in mice by inhibiting the TGF-β1/PI3KCD/MSK2/RELA signalling pathway - Yu-Jia Wu; Wen-Wen Feng; Zhen-Lin Wu; Yue-Yao Zhang; Jin-Yuan Liu; Pei-Ping Xu (Archives of Virology, 2024)

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

Photoreduction of carbon dioxide into methane and ethylene using TiO2 inverse opal-derived PCN-222(M) - Fang-yu Liang; Yen-Ping Peng; Kun-Yi Andrew Lin; Po-Jung Huang (Journal of Environmental Chemical Engineering, 2024)

Selenium-enriched Bifidobacterium longum DD98 significantly improves the efficacy of Mesalazine and Cyclosporin A in colitis mice - Yongjia Hu; Chengchen Xu; Ziqi Xu; Xuan Chen; Fei Gao; Ting Lin; Ping Yang; Shidong Kan; Yu Yin; Daijie Chen (Food Bioscience, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Achieving over 42 % indoor efficiency in wide-bandgap perovskite solar cells through optimized interfacial passivation and carrier transport - Zhong-En Shi; Ta-Hung Cheng; Chien-Yu Lung; Chi-Wei Lin; Chih-Lin Wang; Bing-Huang Jiang; Yu-Sheng Hsiao; Chih-Ping Chen (Chemical Engineering Journal, 2024)

Magneto-elastic for wireless intraocular pressure monitoring - Yu Lin; Shengxin Xiang; Wenjun Zou; Xiaohua Chen; Feixiang Gao; Yi Liu; Yijie Sun; Ping Chen; Quanxi Zhang; Xuelian Han; Baoping Wang; Yong Yao; et al. (Chemical Engineering Journal, 2024)

Unexpected enhancement effects of phosphate on co-immobilization of uranyl arsenate under acidic conditions - Penggang Li; Ping Zhang; Aishu Li; Lin Yu; Mengying Si; Qi Liao; Zhihui Yang; Weichun Yang (Chemical Engineering Journal, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Lnc557 promotes Bombyx mori nucleopolyhedrovirus replication by interacting with BmELAVL1 to enhance its stability and expression - Su Lin; Zhen-Yu Shen; Meng-Dong Wang; Xue-Min Zhou; Tao Xu; Xin-Hao Jiao; Lu-Lai Wang; Xi-Jie Guo; Ping Wu (Pesticide Biochemistry and Physiology, 2024)

MaHOS15 negatively regulates plant immune defense induced by banana fusarium wilt via salicylic acid pathway - Xingchen Jia; Kelin Chen; Yinglong Chen; Yi Tang; Hang Rong; Ping Lin; Yuhao Zhou; Chuqiao Wang; Mingyuan Wang; Jianfu Liu; Qizhi Wang; Hailing Yu (Physiological and Molecular Plant Pathology, 2024)

OsCOPT7 is involved in copper accumulation and transport through xylem - Mei Yan Guan; Zhenzhen Cao; Yu Chun Xia; Ping Xv; Xiao Yan Lin; Ming Xue Chen (Journal of Hazardous Materials, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

The application of a high-density street-level air temperature observation network (HiSAN): Spatial and temporal variations of thermal and wind condition in different climatic condition types - Yu-Cheng Chen; Kai-Shan Hou; Yu-Jie Liao; Tsuyoshi Honjo; Fang-Yi Cheng; Tzu-Ping Lin (Sustainable Cities and Society, 2024)

Dimeric piperidinoquinoline alkaloids from the seeds of Chimonanthus salicifolius - Zhan-Peng Yu; Yu-Xia Wang; Li-Hong Hong; Ya-Lin Li; Jian-Fei Zhang; Mu Li; Ping Ying; Qiang Zheng; Ling-Yi Kong; Jian-Guang Luo (Phytochemistry Letters, 2024)

Dynamic analysis and simulations of a deep-sea floating mining vehicle multi-body system under real-world operating conditions - Jialuan Xiao; Ping Cheng; Junjun Cao; Rui Lin; Mengzhi Luo; Caoyang Yu; Baoheng Yao; Yongli Hu (Ocean Engineering, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Enhancing miso production with optimized puffed-rice koji and its biological function evaluation - Shin-Ping Lin; Yu-Chieh Chou; Chiao-En Chen; Yen-Tso Lai; Chen-Che Hsieh; Tsung-Yu Tsai; Yun-Hsin Lin; Shella Permatasari Santoso; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2024)

Construction and characterization of a novel Myr-OSADS-CIn micelle for enhanced stability and bioavailability of myricetin - Zhi-Yuan Nie; Xue-Ying Li; Ying-Ying Chen; Yuan-Yuan Deng; Dan-Dan Kuang; Yu-Lin Sun; Huan-Huan Xiao; Qiang-Ming Li; Jian-Ping Luo; Xue-Qiang Zha (Food Bioscience, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

A Test System for Microwave-Assisted Dual-Mode Mechanical Cutting of Hard Rock Under True Triaxial Compression - Xia-Ting Feng; Xiang-xin Su; Cheng-xiang Yang; Feng Lin; Shi-ping Li; Jiu-yu Zhang; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)
This paper introduces a test system for microwave-assisted dual-mode mechanical cutting of hard rock under true triaxial compression. The test system was developed by Northeastern University, China, to simulate the cutting and breaking of hard rock by a tunnel boring machine (TBM). The test system is mainly composed of a dual-mode mechanical cutting subsystem, a true triaxial loading subsystem and a high-power microwave presplitting subsystem. The system performs dual-mode cutting under true triaxial stress, applies a single sensor to monitor the three-dimensional force of the cutter head, and integrates the reduction in the vibration and resistance to torsion during the cutting process. Mechanical cutting tests of basalt under different amounts of microwave irradiation and true triaxial stress conditions were conducted in Chifeng, Inner Mongolia, China. The results showed that microwave radiation presplitting effectively improved the efficiency of mechanical rock breaking. However, after 180 s of microwave irradiation, true triaxial high stress inhibited the mechanical breaking of basalt in terms of the overall excavation depth. During the tests, each system performed stably. The test results verified the reliability of the test system.

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

Fluvoxamine Exerts Sigma-1R to Rescue Autophagy via Pom121-Mediated Nucleocytoplasmic Transport of TFEB - Chun-Yu Lin; Hsiang-En Wu; Eddie Feng-Ju Weng; Hsuan-Cheng Wu; Tsung-Ping Su; Shao-Ming Wang (Molecular Neurobiology, 2024)
Expansion of the GGGGCC-RNA repeat is a known cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), which currently have no cure. Recent studies have indicated the activation of Sigma-1 receptor plays an important role in providing neuroprotection, especially in ALS and Alzheimer’s disease. Nevertheless, the mechanisms underlying Sigma-1R activation and its effect on (G 4 C 2 )n-RNA-induced cell death remain unclear. In this study, we demonstrated that fluvoxamine is a Sigma-1R agonist that can increase chaperone activity and stabilize the protein expression of Pom121 in (G 4 C 2 ) 31 -RNA-expressing NSC34 cells, leading to increased colocalization at the nuclear envelope. Interestingly, fluvoxamine treatment increased Pom121 protein expression without affecting transcription. In C9orf72 -ALS, the nuclear translocation of TFEB autophagy factor decreased owing to nucleocytoplasmic transport defects. Our results showed that pretreatment of NSC34 cells with fluvoxamine promoted the shuttling of TFEB into the nucleus and elevated the expression of LC3-II compared to the overexpression of (G 4 C 2 ) 31 -RNA alone. Additionally, even when used alone, fluvoxamine increases Pom121 expression and TFEB translocation. To summarize, fluvoxamine may act as a promising repurposed medicine for patients with C9orf72 -ALS, as it stabilizes the nucleoporin Pom121 and promotes the translocation of TFEB in (G 4 C 2 ) 31 -RNA-expressing NSC34 cells.

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

VGluT2 neuron subtypes in the paraventricular thalamic nucleus regulate depression in paraquat-induced Parkinson’s disease - Yu Zhang; Yihua Jiang; Zhen Yu; Yinhan Li; Xinpei Lin; Yali Weng; Zhenkun Guo; Hong Hu; Wenya Shao; Guangxia Yu; Fuli Zheng; Ping Cai; et al. (Journal of Hazardous Materials, 2024)

The effect of maturity of tea leaves and processing methods on the formation of milky flavor in white tea - A metabolomic study - Jiao Feng; Jiayun Zhuang; Qianlian Chen; Hongzheng Lin; Qiang Chu; Ping Chen; Fang Wang; Bugui Yu; Zhilong Hao (Food Chemistry, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

The origins of odor (β-cyclocitral) under different water nutrient conditions: Algae or submerged plants? - Yu Lin; Chaoyue Cheng; Yutai Dai; Weijie Li; Jiping Chen; Mo Chen; Ping Xie; Qiang Gao; Xiaoyue Fan; Xuwei Deng (Science of The Total Environment, 2024)

Postvaccination serosurveillance of foot-and-mouth disease through virus-neutralizing and nonstructural protein antibody tests on pig farms in Taiwan: 2009–2020 - Ming-Chang Lee; Yu-Fen Sun; Ming-Chung Deng; Nien-Nung Lin; Jung-Pin Hsu; Chwei-Jang Chiou; Wen-Jane Tu; Shih-Ping Chen (Preventive Veterinary Medicine, 2024)

Estrogen-related receptor, a molecular target against lepidoptera pests - Guan Wang Shen; Die Liu; Hao Ran Xu; Lu Yu Hou; Jin Xin Wu; Qing You Xia; Ping Lin (Pesticide Biochemistry and Physiology, 2024)

Isolation of undescribed cladosporols and spirobisnaphthalenes from a plant pathogen Cladosporium cladosporioides F-10-2-A - Peng Li; Zi Jin Zhang; Yu Tong Guo; Jing Guan; Lin Bo Wen Xi; Li-Ping Lin (Phytochemistry, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

First record of the late Famennian conodonts in Qamdo, Tibet and their biostratigraphic implications - Yu-Ze Huang; Wen Guo; Wei Lin; Ping-Cuo Zhaxi; Le Yao; Ke-Yi Hu; Qiu-Lai Wang; Yu-Ping Qi (Palaeoworld, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

MetaIBM: A Python-based library for individual-based modelling of eco-evolutionary dynamics in spatial-explicit metacommunities - Jian-Hao Lin; Yu-Juan Quan; Bo-Ping Han (Ecological Modelling, 2024)

CuO NWs boosted triboelectric microfluidic nanosensor functionalized by collagen-protein interactions for real-time platelet count monitoring - Jia-Cheng Lin; Kuldeep Kaswan; Subhodeep Chatterjee; Yu-Wen Wu; Manish Kumar Sharma; Ashok Ranjan; Snigdha Roy Barman; Yu-Zih Lin; Thierry Burnouf; Wilfrid Boireau; Ming-Yen Lu; Yong-Kwang Tu; et al. (Chemical Engineering Journal, 2024)

Implementing policies to mitigate urban heat islands: Analyzing urban development factors with an innovative machine learning approach - Shiang-Yu Wang; Hsing-Yu Ou; Ping-Chun Chen; Tzu-Ping Lin (Urban Climate, 2024)

Medial amygdala NRG1 signaling mediates adolescent social isolation-induced autistic-like behaviors - Lian-Hong Lin; Qian-Yun Wu; Kai Zeng; Zi-Yu Chen; Zi-Ping Wang; Wei-Min Li; Bin Zhang; Tian-Ming Gao; Ji-Hong Liu (Science Bulletin, 2024)

Highly modified cephalotane-type diterpenoids from Cephalotaxus fortunei var. alpina and C. sinensis - Zhan-Peng Ge; Jin-Biao Xu; Peng Zhao; Mai Xiang; Yu Zhou; Ze-Min Lin; Jian-Ping Zuo; Jin-Xin Zhao; Jian-Min Yue (Phytochemistry, 2024)

Nanozyme sensor array based on Fe, Se co-doped carbon material for the discrimination of Sulfur-containing compounds - Enxiang Ren; Haochen Qiu; Zhixuan Yu; Min Cao; Muhammad Sohail; Guo-Ping Lu; Xing Zhang; Yamei Lin (Journal of Hazardous Materials, 2024)

Decoding the genome of bloodsucking midge Forcipomyia taiwana (Diptera: Ceratopogonidae): Insights into odorant receptor expansion - Ming-Der Lin; Chia-Hsien Chuang; Chih-Hsin Kao; Shu-Hwa Chen; Szu-Chieh Wang; Ping-Heng Hsieh; Guan-Yu Chen; Chun-Chia Mao; Jeng-Yi Li; Mei-Yeh Jade Lu; Chung-Yen Lin (Insect Biochemistry and Molecular Biology, 2024)

Investigation into the potential mechanism of Bacillus amyloliquefaciens in the fermentation of broad bean paste by metabolomics and transcriptomics - Hongbin Lin; Shiqi Liao; Zesu Zhou; Ziting Yan; Jianhua Zhao; Yue Xiang; Min Xu; Jie Zhao; Ping Liu; Wengwu Ding; Yu Rao; Jie Tang (Food Research International, 2024)

LncRNA NR_030777 promotes mitophagy by targeting CDK1-related mitochondrial fission and ATG12 to attenuate paraquat-induced Parkinson's disease - Nengzhou Chen; Hong Hu; Jianping Tang; Fuli Zheng; Zhenkun Guo; Xinpei Lin; Michael Aschner; Wenya Shao; Guangxia Yu; Ping Cai; Wei-Chun Chou; Siying Wu; et al. (Environmental Pollution, 2024)

Regulating photoluminescence through single-crystal-to-single-crystal transformation of solvent-containing zero-dimensional hybrid metal halide isomers - Ying-Chen Peng; Jian-Ce Jin; Sheng-Hua Zhou; Hao-Wei Lin; Dan-Dan Huang; Zhong-Hua Deng; Yu Dong; Hao-Jie Xu; Ke-Zhao Du; Ze-Ping Wang; Xiao-Ying Huang (Chemical Engineering Journal, 2024)

CFD simulation of pumping ventilation with two asymmetrically arranged openings on the rear wall in a three-story isolated building - Huai-Yu Zhong; Jie Sun; Chao Lin; Hideki Kikumoto; Wei Dong; Yang Cai; Fu-Yun Zhao; Song-Heng Wu; Fu-Ping Qian (Building and Environment, 2024)

Potassium diformate alleviated inflammation of IPEC-J2 cells infected with EHEC - Ying Lin; Jun-Lei Zhai; Ya-Ting Wang; Ping-Ting Guo; Jing Zhang; Chang-Kang Wang; Ling Jin; Yu-Yun Gao (Veterinary Microbiology, 2024)

Enhancing acid stability of citral through internal structure modulation in nanostructured lipid carriers with solid lipids and phospholipids - Simin Feng; Jialu Sheng; Jiahao Yu; Yang Lin; Ping Shao (Food Research International, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Morphology and chemical composition of Taiwan oil millet (Eccoilopus formosanus) epicuticular wax - Marita Anggarani; Yu-Ying Lin; Shao-An Fang; Hshin-Ping Wu; Chi-Chih Wu; Wann-Neng Jane; Thomas James Roscoe; Frederic Domergue; Yue-Ie Caroline Hsing (Planta, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

A hybrid system for Nickel ions removal from synthesized wastewater using adsorption assisted with electrocoagulation - Jean Claude Nizeyimana; Pamphile Ndagijimana; Junaid Khan; Liu Xiangru; Gratien Twagirayezu; Habasi Patrick Manzi; Olivier Irumva; Chang-Ping Yu; Anyi Hu; Shanshan Lin (Environmental Science and Pollution Research, 2024)

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

Upgrading swin-B transformer-based model for accurately identifying ripe strawberries by coupling task-aligned one-stage object detection mechanism - Huan Liu; Xiaoxuan Wang; Feiyu Zhao; Feiyang Yu; Ping Lin; Yang Gan; Xuefeng Ren; Yongming Chen; Jian Tu (Computers and Electronics in Agriculture, 2024)

Long-term biogas slurry application increases microbial necromass but not plant lignin contribution to soil organic carbon in paddy soils as regulated by fungal community - Zhaoming Chen; Jinchuan Ma; Junwei Ma; Jing Ye; Qiaogang Yu; Ping Zou; Wanchun Sun; Hui Lin; Feng Wang; Xinlin Zhao; Qiang Wang (Waste Management, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Development of a rapid visual detection technology for BmNPV based on CRISPR/Cas13a system - Xue-Min Zhou; Zhen-Yu Shen; Yi-Xiang Wu; Su Lin; Meng-Dong Wang; Tao Xu; Lu-Lai Wang; Samreen Sadiq; Xin-Hao Jiao; Ping Wu (Journal of Invertebrate Pathology, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Co-occurrence of organophosphate esters and phosphorus fractions in river sediments: Implications for pollution prediction and environment risk assessment - Lingfang Fu; Yuxin Liu; Shu Lin; Jieer Xiao; Weijie Li; Yang Yu; Hailong Zeng; Ping Li; Huaiyang Fang (Journal of Hazardous Materials, 2024)

Agar-altered foaming bacterial cellulose with carvacrol for active food packaging applications - Anita Chandra Kusuma; Yu-Chieh Chou; Chen-Che Hsieh; Shella Permatasari Santoso; Alchris Woo Go; Hong-Ting Victor Lin; I.-Lun Hsiao; Shin-Ping Lin (Food Packaging and Shelf Life, 2024)

Corrigendum to “Effects of interface conditions on tribological and hysteretic behaviors of symmetric friction connections” Eng Struct 302 (2024) 117405 - Hongliang Liu; Liang-Jiu Jia; Yu-Ao Lin; Ping Xiang (Engineering Structures, 2024)

Effects of interface conditions on tribological and hysteretic behaviors of symmetric friction connections - Hongliang Liu; Liang-Jiu Jia; Yu-Ao Lin; Ping Xiang (Engineering Structures, 2024)

Experimental study on strength characteristics and constitutive behavior of frozen chloride silty clay - Yu Tang; Ping Yang; Lin Li; Zhiliang Zhou (Cold Regions Science and Technology, 2024)

A global synthesis of the patterns of genetic diversity in endangered and invasive plants - Zhi-Zhou He; Gisela C. Stotz; Xiang Liu; Jia-Jia Liu; Yu-Guo Wang; Ji Yang; Lin-Feng Li; Wen-Ju Zhang; Peng Nan; Zhi-Ping Song (Biological Conservation, 2024)

Optimization of Microwave Presplitting Iron Ore to Improve Mechanical Mining Efficiency - Feng Lin; Xia-ting Feng; Shi-ping Li; Jiu-yu Zhang; Xiang-xin Su; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)

Heteronemin promotes iron-dependent cell death in pancreatic cancer - Gizem Kaftan; Mümin Alper Erdoğan; Mohamed El-Shazly; Mei-Chin Lu; Shou-Ping Shih; Hung-Yu Lin; Luciano Saso; Güliz Armagan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Rapid identification and characterization of pineapple fruitlet core rot pathogens on the ‘TN20’ cultivar in Taiwan - Yu-Ping Liang; Kuan-Yu Lin; Su-Yu Lai; Hui-Fang Ni (European Journal of Plant Pathology, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Overdose with the anesthetic propofol causes hematological cytotoxicity and immune cell alteration in an experimental ex vivo whole blood culture model - Chung-Hsi Hsing; Yu-Ping Hung; Ming-Chung Lin; Chia-Ling Chen; Yung-Ting Wang; Po-Chun Tseng; Rahmat Dani Satria; Chiou-Feng Lin (Toxicology in Vitro, 2024)

Efficient and cost-effective method for identifying urban ventilation corridors using a heuristic search algorithm - Tsz-Kin Lau; Pei-Chi Tsai; Hsing-Yu Ou; Tzu-Ping Lin (Sustainable Cities and Society, 2024)

Tri-objective Stochastic Model to Optimize Location and Sizing of Scooter Battery Swapping Station - Yu-Hao Lin; Ping-Yu Liu; Chieh-Feng Chiang (Sustainable Cities and Society, 2024)

Comparison of four pre-oxidants coupled powdered activated carbon adsorption for odor compounds and algae removal: Kinetics, process optimization, and formation of disinfection byproducts - Heng-Xuan Zhao; Shuang Zhang; Tian-Yang Zhang; Yi-Ping Zhu; Ren-Jie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Science of The Total Environment, 2024)

Shrimp SIRT4 promotes white spot syndrome virus replication - Yu Kent Tan; Brandon Rafael de Jesús Castillo-Corea; Ramya Kumar; Ping-Hung Lai; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2024)

Effect of stress on the rehabilitation performance of rats with repetitive mild fluid percussion-induced traumatic brain injuries - Yu-Lin Wang; Chi-Chun Chen; Ching-Ping Chang (Cognitive Neurodynamics, 2024)

Effects of dietary betaine supplementation on growth performance, feed intake, intestinal histology, lipid metabolism, and immune response of black tiger shrimp (Penaeus monodon) fed diets containing two levels of raw feed attractants - Gui-Lun He; Meng-Lin Shi; Yu-Cheng Liu; Liu-Tong Chen; Xin Chen; Wen-Bo Zhu; Zheng-Bang Chen; Bei-Ping Tan; Shi-Wei Xie (Aquaculture International, 2024)

Effects of Different Intensities and Wavelengths of Light on the Growth of Juvenile Tridacna noae - Rod Ping-Tsan Lee; Yu-Ru Lin; Chih-Yang Huang; Fan-Hua Nan (Molluscan Research, 2024)

Long-term exposure to polystyrene microplastics induces hepatotoxicity by altering lipid signatures in C57BL/6J mice - Jiawen Tao; Ping Deng; Min Lin; Chunhai Chen; Qinlong Ma; Lingling Yang; Wenjuan Zhang; Yan Luo; Siyu Chen; Huifeng Pi; Zhou Zhou; Zhengping Yu (Chemosphere, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Reciprocal transplant experiment reveals multiple factors influencing changes in coral microbial communities across climate zones - Ya-Fan Chan; Yu-Hsiang Chen; Sheng-Ping Yu; Hsing-Ju Chen; Yoko Nozawa; Sen-Lin Tang (Science of The Total Environment, 2024)

The application of strategy based on LSTM for the short-term prediction of PM2.5 in city - Min-Der Lin; Ping-Yu Liu; Chi-Wei Huang; Yu-Hao Lin (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

Encapsulation and release of citral using nanostructured lipid carriers: A study on the impact of different preparation methods - Simin Feng; Jialu Sheng; Jiahao Yu; Yang Lin; Ping Shao (Food Bioscience, 2023)

Enhanced resuscitation of anammox granular sludge by adding folate: A perspective from the growth factor - Chao Pan; Leiyan Guo; Yang Yu; Wenji Li; Dongdong Xu; Wenda Chen; Lin Zhu; Baolan Hu; Ping Zheng; Meng Zhang (Chemical Engineering Journal, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Transcranial Alternating Current Stimulation in a Patient with Ataxia-Ocular Apraxia 2: a Case Report - Xiao-Ping Cheng; Wen-Hui Yu; Xia Liu; Wei Lin; Zhao-Di Wang; Xi-Chen Wang; Jun Ni; Nai-Qing Cai; Xin-Yuan Chen (The Cerebellum, 2023)

Association of mono-2-ethylhexyl phthalate with adverse outcomes in chronic hemodialysis patients - Chia-Lin Wu; Yu-Wei Fang; Yi-Chou Hou; Kuo-Cheng Lu; Wen-Hsin Tsai; Ping-Hsun Lu; Tzong-Shyuan Lee; Ko-Lin Kuo (Environmental Science and Pollution Research, 2023)
Phthalate exposure is widespread and has a global impact. Growing evidence shows that mono-2-ethylhexyl phthalate (MEHP) exposure has a negative impact on human health. However, whether MEHP exposure is associated with mortality and other adverse outcomes in hemodialysis patients remains unknown. This study prospectively enrolled 217 patients on maintenance hemodialysis from June 30, 2021, to August 16, 2022. Baseline serum MEHP, di-2-ethylhexyl phthalate (DEHP), and indoxyl sulfate (IS) concentrations were measured. Primary endpoints were all-cause mortality or composite adverse outcomes, including all-cause death plus hospitalization due to cardiovascular disease, heart failure, stroke, infection, or cancer. Serum MEHP concentrations were positively associated with DEHP but not indoxyl sulfate concentrations in hemodialysis patients. Additionally, serum MEHP concentrations were significantly and independently associated with all-cause mortality and composite adverse outcomes (adjusted hazard ratios [HRs], 1.04 and 1.03 per ng/mL, 95% confidence intervals [CIs], 1.01–1.07 and 1.00–1.05; p = 0.016 and 0.015, respectively). We found a cutoff value of MEHP for predicting both endpoints. Patients with serum MEHP concentrations of ≥ 41.8 ng/mL had much higher risks for all-cause mortality and composite adverse outcomes (adjusted HRs, 39.2 and 13; 95% CIs, 2.44–65.7 and 2.74–61.4; p = 0.011 and 0.001, respectively). MEHP exposure is significantly associated with higher risks for all-cause mortality and composite adverse outcomes. Hemodialysis patients with serum MEHP concentrations above 41.8 ng/mL had much poorer prognoses regarding both outcomes.

Applying sheet iron to enhance the treatment efficiency of digested effluent with continuous flow and the corresponding mechanism - Cong Ding; Li-bin Chen; Li-ping Yu; Ru Wang; Lin-jiang Yuan; Lan Wang; Liang-wei Deng (Chemosphere, 2023)

Application of local climate zones combined with machine learning to predict the impact of urban structure patterns on thermal environment - Tsz-Kin Lau; Yu-Cheng Chen; Tzu-Ping Lin (Urban Climate, 2023)

Chronic cadmium exposure induces Parkinson-like syndrome by eliciting sphingolipid disturbance and neuroinflammation in the midbrain of C57BL/6J mice - Yudong Xu; Huihui Hong; Xiqin Lin; Tong Tong; Jingjing Zhang; Haotian He; Lingling Yang; Gaofeng Mao; Rongrong Hao; Ping Deng; Zhengping Yu; Huifeng Pi; et al. (Environmental Pollution, 2023)

Silver nanoparticle@catechol formaldehyde resin microspheres: One-pot synthesis and application for producing durable antimicrobial cotton fabrics - Lian-Yi Qu; Jiang-Long Liu; An-Le Yang; Lin Zhang; Ping Zhu; Ying-Jun Xu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Transcriptome Analysis Revealed the Differential Molecular Response Mechanisms of Roots, Stems, and Leaves in Mung Bean to Cadmium Stress - Ping-min Wu; Yan Leng; Shi-Weng Li; Yu-Lin Wang; Fu-Jun Qiao (Journal of Plant Growth Regulation, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Bi0·5Na0·5TiO3/ZnO Z-scheme heterojunction for piezo-photocatalytic water remediation: Mechanical energy harvesting and energy band configuration - Peng Wang; Wanqian Cai; Fangyuan Yu; Ping Zhou; Mei Lin; Cong Lin; Tengfei Lin; Min Gao; Chunlin Zhao; Xiangqi Li; Xiao Wu (Chemosphere, 2023)

Simplified synthesis of direct Z-scheme Bi2WO6/PhC2Cu heterojunction that shows enhanced photocatalytic degradation of 2,4,6-TCP: Kinetic study and mechanistic insights - Jinfan Zhang; Zili Lin; Zongshun Yu; Yudan Zhang; Danluo Liang; Yingyi Chen; Yu Chen; Ping Chen; Haijin Liu; Wenying Lv; Guoguang Liu (Journal of Hazardous Materials, 2023)

Valorization of heavy metal-adsorbed microalgae from a membrane bioreactor for levulinic acid production - Chung-Yu Guan; Yen-Lin Kao; Van Toi Pham; Pei-Hsun Wu; Chang-Ping Yu (Journal of Environmental Chemical Engineering, 2023)

Biocontrol of Salmonella Typhimurium in milk, lettuce, raw pork meat and ready-to-eat steamed-chicken breast by using a novel bacteriophage with broad host range - Junxin Zhao; Yunzhi Lin; Chen Wang; Mahmoud Zayda; Aye Thida Maung; Tahir Noor Mohammadi; Hoang Minh Duc; Ping Yu; Maomao Ma; Deming Gong; Jun Sato; Yoshimitsu Masuda; et al. (International Journal of Food Microbiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Loss of OsARF18 function confers glufosinate resistance in rice - Jin-Qiu Xia; Da-Yu He; Qin-Yu Liang; Zheng-Yi Zhang; Jie Wu; Zi-Sheng Zhang; Jing Zhang; Lin Wang; Cong-He Zhang; Ping-Xia Zhao; Cheng-Bin Xiang (Molecular Plant, 2023)

CDN1163, a SERCA activator, causes intracellular Ca2+ leak, mitochondrial hyperpolarization and cell cycle arrest in mouse neuronal N2A cells - Yi-Ping Huang; Wen-Wei Huang; Kun-Feng Tsai; Lian-Ru Shiao; Zih-He Yang; Shao-Yun Tseng; Yu-Hsien Lin; Cing-Yu Chen; Paul Chan; Yuk-Man Leung (NeuroToxicology, 2023)

Key role of Fe(VI)-activated Bi2WO6 in the photocatalytic oxidation of sulfonamides: Mediated electron transfer mechanism - Yudan Zhang; Ping Chen; Wenying Lv; Zhenjun Xiao; Jinfan Zhang; Jianqing Wu; Zili Lin; Guangzhi Zhang; Zongshun Yu; Haijin Liu; Guoguang Liu (Journal of Hazardous Materials, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

In-situ gas flow separation between biochar and the heat carrier in a circulating fluidized bed reactor for biomass pyrolysis - Zheng-hao Yang; Zhen He; Xiang-gang Zhang; Xia Jiang; Zi-heng Jin; Jian-ping Li; Liang Ma; Hua-lin Wang; Yu-long Chang (Chemical Engineering Journal, 2023)

Plasma-activated silicon–glass high-strength multistep bonding for low-temperature vacuum packaging - Mingzhi Yu; Libo Zhao; Yongliang Wang; Yong Xia; Yintao Ma; Yanbin Wang; Xiangguang Han; Yao Chen; Shun Lu; Guoxi Luo; Nan Zhu; Ping Yang; et al. (Chemical Engineering Journal, 2023)

Effects of orientation and dimensions of shading structures on thermal comfort - Hsing-Yu Ou; Tzu-Ping Lin (Building and Environment, 2023)

Harnessing split fluorescent proteins in modular protein logic for advanced whole-cell detection - Ping-Heng Lin; Ssu-Tzu Tsai; Yu-Chia Chang; Yi-Ju Chou; Yi-Chun Yeh (Analytica Chimica Acta, 2023)

Evolutionary roles of polyploidization‐derived structural variations in the phenotypic diversification of Panax species - Yu‐Xin Zhang; Xin‐Feng Wang; Yu‐Qian Niu; Yu‐Guo Wang; Wen‐Ju Zhang; Zhi‐Ping Song; Ji Yang; Lin‐Feng Li (Molecular Ecology, 2023)
Genomic structural variations (SVs) are widespread in plant and animal genomes and play important roles in phenotypic novelty and species adaptation. Frequent whole genome duplications followed by (re)diploidizations have resulted in high diversity of genome architecture among extant species. In this study, we identified abundant genomic SVs in the Panax genus that are hypothesized to have occurred through during the repeated polyploidizations/(re)diploidizations. Our genome‐wide comparisons demonstrated that although these polyploidization‐derived SVs have evolved at distinct evolutionary stages, a large number of SV‐intersecting genes showed enrichment in functionally important pathways related to secondary metabolites, photosynthesis and basic cellular activities. In line with these observations, our metabolic analyses of these Panax species revealed high diversity of primary and secondary metabolites both at the tissue and interspecific levels. In particular, genomic SVs identified at ginsenoside biosynthesis genes, including copy number variation and large fragment deletion, appear to have played important roles in the evolution and diversification of ginsenosides. A further herbivore deterrence experiment demonstrated that, as major triterpenoidal saponins found exclusively in Panax , ginsenosides provide protection against insect herbivores. Our study provides new insights on how polyploidization‐derived SVs have contributed to phenotypic novelty and plant adaptation.

Distribution and potential health risks of perfluoroalkyl substances (PFASs) in water, sediment, and fish in Dongjiang River Basin, Southern China - Wang Xu; Shibo Li; Weimin Wang; Ping Sun; Chunyang Yin; Xuxia Li; Liang Yu; Gang Ren; Lin Peng; Fei Wang (Environmental Science and Pollution Research, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

The sustainable treatment of chemical polishing wastewater under low-carbon economy: Pollutants removal, resource recovery and energy generation - Cong Ding; Meng-yu Liu; Si-zhuo Wan; Zhao-yang Cai; Lin-jiang Yuan; Ru Wang; Ping Zheng (Journal of Cleaner Production, 2023)

Four cases of reported adverse effects from black boletoi, Anthracoporus nigropurpureus (Boletaceae) mushroom ingestion - Jing Ma; Jing Xia; Hai-Jiao Li; Lin-Jie Su; Rou Xue; Shuai Jiang; Tai-Jie Yu; Yi Liu; Li-Ping Tang (Toxicon, 2023)

Influence of microclimate control on the growth of asparagus under greenhouse in tropical climates - Kuo-An Hung; Yi-Wei Hsu; Yu-Cheng Chen; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

Conservation tillage increases surface soil organic carbon stock by altering fungal communities and enzyme activity - Wen-Sheng Liu; Yu-Xin Wei; Ping-Ping Deng; Olatunde Pelumi Oladele; Yves N’Dri Bohoussou; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (Environmental Science and Pollution Research, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Confined self-assembly of S, O co-doped GCN short nanotubes/EG composite towards HMIs electrochemical detection and removal - Jue Wang; Kan Kan; Ping Yu; Yihe Fan; Jiahui Fan; Lin Jiang; Fangjie Qin; Keying Shi (Journal of Hazardous Materials, 2023)

Ecofriendly removal of Lead, Cadmium and Arsenic along with turbidity from contaminated water using natural reservoir clay (NRC) and S. pasteurii derived urease - Jyoti Prakash Maity; Yung-Ping Chen; Jirawadee Promsri; Yi-Hsun Huang; Raju Kumar Sharma; Yu-Hui Chen; Pin-Yun Lin; Marut Tangwattanachuleeporn; Kulwara Poolpol; Tsung-Hsien Chen; Chien-Yen Chen (Desalination, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Structural, mechanical and thermal properties of cubic bixbyite-structured high-entropy oxides - Xinyu Ping; Bin Meng; Xiaohua Yu; Zhiyuan Ma; Xiaoyu Pan; Wu Lin (Chemical Engineering Journal, 2023)

Undescribed phloroglucinol derivatives with antiviral activities from Dryopteris atrata (Wall. Ex Kunze) Ching - Ji-hui Zhang; Jin-lin Chen; Wei-bin Xu; Yi-ping Xia; Hao-yue Zhu; Jing-hao Wang; Yao-lan Li; Guo-cai Wang; Yu-bo Zhang; Neng-hua Chen (Phytochemistry, 2023)

Iron catalyzed organic reactions in water: A “nature-like” synthesis - Fuying Zhu; Guo-Ping Lu; Fei Wang; Enxiang Ren; Yueyi Yu; Yamei Lin (Current Opinion in Green and Sustainable Chemistry, 2023)

Eicosane-based thermo-conductive phase change composite for efficient capture solar energy and using in real-environment as power source - Linhong Li; Maohua Li; Yue Qin; Yapeng Chen; Wen Dai; Zhenbang Zhang; Xiangdong Kong; Ping Gong; Yandong Wang; Rongjie Yang; Bo Wang; Tao Cai; et al. (Chemical Engineering Journal, 2023)

The ability of pre-magnetized zero-valent iron for peroxymonosulfate activation to remove ofloxacin - Yang Wu; Jing-ying Zhu; Jia-wen Bai; Li-feng Lin; Chang-ping Yu (Chemical Engineering Journal, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Coenzyme Q0 defeats NLRP3-mediated inflammation, EMT/metastasis, and Warburg effects by inhibiting HIF-1α expression in human triple-negative breast cancer cells - Hsin-Ling Yang; Ping-Yu Lin; Chithravel Vadivalagan; Yi-An Lin; Kai-Yuan Lin; You-Cheng Hseu (Archives of Toxicology, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Halogen microregulation in metal-organic frameworks for enhanced adsorption performance of ReO4-/TcO4- - Qing-Hua Hu; You-Gan Wang; Xin Gao; Yu-Zhen Shi; Sen Lin; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Effect of defects in adhesive layer on the interfacial bond behaviors of externally bonded CFRP-to-concrete joints - Peng-Da Li; Yao Zhao; Yu-Fei Wu; Jian-Ping Lin (Engineering Structures, 2023)

Preparation of alumina/silica/exfoliated graphite nanoplatelets composite aerogels and its application as supporting material for erythritol based form-stable phase change materials - Yu-Hao Ning; Ye Tan; Chuan-Huang Lin; Qi Li; Lin-Ping Yu; Zhong Cao; Li-Xian Sun; Chuan-Chang Li; Ju-Lan Zeng (Chemical Engineering Journal, 2023)

Correction to: Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2023)

New remains of Ailuropoda melanoleuca baconi from Yanjinggou, China: Throwing light on the evolution of giant pandas during the Pleistocene - Haiqian Hu; Haowen Tong; Qingfeng Shao; Guangbiao Wei; Haidong Yu; Jingsong Shi; Xunqian Wang; Can Xiong; Yu Lin; Ning Li; Zhaoying Wei; Ping Wang; et al. (Journal of Mammalian Evolution, 2023)

Performance and mechanism of GO removal by gypsum from aqueous solution - Ping Jiang; Guanzhong Zhou; Cuihong Li; Yanfei Yu; Lin Zhou; Haibo Kang (Environmental Science and Pollution Research, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Antibacterial activity and mechanism of action of bacteriocin LFX01 against Staphylococcus aureus and Escherichia coli and its application on pork model - Wei-Gang Xin; Gang Wu; Jian-Ping Ying; Yi-Zhou Xiang; Yu-Hang Jiang; Xian-Yu Deng; Lian-Bing Lin; Qi-Lin Zhang (Meat Science, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Spatial distribution and driving factors of sediment net nitrogen mineralization in riparian zone of the Three Gorges Reservoir - Kai-tao Jia; Li-ping He; Ke-hong Wang; Zhi-guo Yu; Li-jiao Liang; Zhuo-lin Yu; Jun-jie Lin (Journal of Mountain Science, 2023)

Differential responses of soil nirS- and nirK-type denitrifying microbial communities to long-term application of biogas slurry in a paddy soil - Zhaoming Chen; Jinchuan Ma; Yinxiu Liu; Jun Zhao; Junwei Ma; Qiaogang Yu; Ping Zou; Hui Lin; Qiang Wang (Applied Soil Ecology, 2023)

Temperature-dependent effects of neonicotinoids on the embryonic development of zebrafish (Danio rerio) - Yolina Yu Lin Wang; Yan-Er Cai; Syed Shabi Ul Hassan Kazmi; Jing Yang; Yuwen Wang; Ping Li; Wenhua Liu; Zhen Wang (Frontiers in Marine Science, 2023)
The agricultural use of neonicotinoids is increasing worldwide and poses a threat to non-target organisms. The existing toxicity data of neonicotinoids that is mainly focused on widely used neonicotinoids ignores the influence of environmental factors, like temperature, related to climate changes, etc . To fill this data gap, the present study assessed the temperature-dependent toxicity of six neonicotinoids at four temperatures. Briefly, a fish embryo toxicity test was performed at the following temperatures—20, 23, 28, and 33°C—on zebrafish embryos to evaluate the lethal and sublethal effects of these toxicants. At 28°C, the lethal toxicity (LC 50 ) values for these toxicants were cycloxaprid—3.36 mg/L, nitenpyram—7.08 mg/L, paichongding—17.2 mg/L, imidaclothiz—738.6 mg/L, dinotefuran—2,096 mg/L, and thiamethoxam—4,293 mg/L, respectively. Among the sublethal effects, the enzymatic activities changed significantly in neonicotinoid treatments, which revealed oxidative stress, metabolic disorders, and neurotoxicity. Particularly, acetylcholinesterase inhibition and glutathione S-transferase activation showed a significant dose–response relationship. However, cycloxaprid, nitenpyram, and paichongding were found to be more potent compared with imidaclothiz and thiamethoxam. The influence of temperature on these neonicotinoids demonstrated an inverted V-shaped relationship, in which toxicity decreased with the increase of temperature and then increased with the increase of temperature after exceeding the optimum temperature. This study provides a reference for the multiscale effects and potential mechanisms of neonicotinoids. Temperature-dependent toxicity is of great significance for future toxicity testing and risk assessment of chemicals in the face of global climate changes.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Environmental concentrations of benzophenone-3 disturbed lipid metabolism in the liver of clown anemonefish (Amphiprion ocellaris) - Yan-Kun Zhang; Huai-Yang Ke; Yong-Qiang Qin; Han-Ye Ju; Yu-Mei Chen; Fang Lin; Ji-Liang Zhang; Xiao-Ping Diao (Environmental Pollution, 2023)

Lightweight Flexible Polyimide-Derived Laser-Induced Graphenes for High-Performance Thermal Management Applications - Yu-Sheng Hsiao; Cai-Wan Chang-Jian; Tzu-Yen Huang; Ying-Lin Chen; Chung-Wei Huang; Jen-Hsien Huang; Nian-Jheng Wu; Shih-Chieh Hsu; Chih-Ping Chen (Chemical Engineering Journal, 2023)

Temperature tolerant all-solid-state touch panel with high stretchablity, transparency and self-healing ability - Zhenglin Chen; Fang Li; Likun Zhang; Zhengyang Lei; Canhui Yang; Chufan Xiao; Lijin Lian; Xi Yuan; Gul Ijaz; Jia'e Yang; Zijun Lin; Yunfeng He; et al. (Chemical Engineering Journal, 2023)

Hydroxychloroquine repairs burn damage through the Wnt/β-catenin pathway - Sheau-Chung Tang; Chun-Te Lu; Jiunn-Liang Ko; Cheng-Hui Lin; Yu-Ping Hsiao (Chemico-Biological Interactions, 2023)

Combined analysis of mRNA and miRNA reveals the banana potassium absorption regulatory network and validation of miRNA160a - Wenliang Chen; Tao Dong; Yinglong Chen; Ping Lin; Chuqiao Wang; Kelin Chen; Yi Tang; Mingyuan Wang; Jianfu Liu; Hailing Yu (Plant Molecular Biology, 2022)

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

Two new sesquiterpenoid lactone derivatives from Lindera aggregata - Song-Song Wen; Yan Wang; Jia-Ping Xu; Qi Liu; Lei Zhang; Jing Zheng; Lin Li; Na Zhang; Xin Liu; Yu-Wen Xu; Zhen-Liang Sun (Natural Product Research, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

The Influence of the Rotary Speed of a Microwave Applicator on Hard-Rock Fracturing Effect - Xia-ting Feng; Shi-ping Li; Cheng-xiang Yang; Feng Lin; Tian-yang Tong; Xiang-xin Su; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2022)

Methods to control harmful algal blooms: a review - Barathan Balaji-Prasath; Ying Wang; Yu Ping Su; David P. Hamilton; Hong Lin; Luwei Zheng; Yong Zhang (Environmental Chemistry Letters, 2022)

Role of ocean dynamics in equatorial Pacific decadal variability - Yu Zhang; Shi-Yun Yu; Shang-Ping Xie; Dillon J. Amaya; Qihua Peng; Yu Kosaka; Xiaopei Lin; Jun-Chao Yang; Sarah M. Larson; Arthur J. Miller; Lei Fan (Climate Dynamics, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Breast Cancer Awareness Based on Health Information Literacy and Influential Factors among Female Nursing Students in China - Shu Yang; Ping Li; Lin Yu; Na Liu; Jie Wang; Pingping Guo; Xuehui Zhang; Wei Zhang (Journal of Cancer Education, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Preliminary study of genome-wide association identifies novel susceptibility genes for serum mineral elements in the Chinese Han population - Duojian Guo; Yu Zhou; Xingwei Wei; Shanshan Zhang; Tianbo Jin; Yutian Zhang; Mei Lin; Xiaoli Zhou; Yufei Xie; Chanyi He; Qi Lin; Ping He; et al. (Biological Trace Element Research, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Effects of Involuntary and Voluntary Exercise in Combination with Acousto-Optic Stimulation on Adult Neurogenesis in an Alzheimer's Mouse Model - Wan-yi Li; Jun-yan Gao; Su-Yang Lin; Shao-tao Pan; Biao Xiao; Yu-tao Ma; Kai Xie; Wei Shen; Zhi-tao Liu; Guang-yu Li; Jie-jie Guo; Qin-wen Wang; et al. (Molecular Neurobiology, 2022)

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Hippocampal SIRT1-Mediated Synaptic Plasticity and Glutamatergic Neuronal Excitability Are Involved in Prolonged Cognitive Dysfunction of Neonatal Rats Exposed to Propofol - Lin-Hui Ma; Jie Wan; Jing Yan; Ning Wang; Yan-Ping Liu; Hai-Bi Wang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2022)

Fate of heavy metals and bacterial community composition following biogas slurry application in a single rice cropping system - Qiang Wang; Zhaoming Chen; Jun Zhao; Junwei Ma; Qiaogang Yu; Ping Zou; Hui Lin; Jinchuan Ma (Journal of Soils and Sediments, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Characterization of alkaloids in radix Sophora tonkinensis by UPLC-Q-TOF-MS/MS and its application in the comparison of two different habitats - Xing-Xing Zong; Yu Wang; Jia-Liang Xiong; Yu-Hui Ping; Qiong-Lin Liang (Natural Product Research, 2022)

Novel wing display and divergent agonistic behaviors of two incipient Psolodesmus damselflies - Leocris S. Batucan; Yu-Hsun Hsu; Jak W. Maliszewski; Liang-Jong Wang; Chung-Ping Lin (The Science of Nature, 2021)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

Protective effect of Bombyx mori gloverin on intestinal epithelial cells exposure to enterotoxigenic E. coli - Qian Lin; Qingqing Fu; Guoqi Su; Daiwen Chen; Bing Yu; Yuheng Luo; Ping Zheng; Xiangbing Mao; Zhiqing Huang; Jie Yu; Junqiu Luo; Hui Yan; et al. (Brazilian Journal of Microbiology, 2021)

Performance Comparison of the Deep Learning and the Human Endoscopist for Bleeding Peptic Ulcer Disease - Hsu-Heng Yen; Ping-Yu Wu; Pei-Yuan Su; Chia-Wei Yang; Yang-Yuan Chen; Mei-Fen Chen; Wen-Chen Lin; Cheng-Lun Tsai; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2021)
Purpose Management of peptic ulcer bleeding is clinically challenging. Accurate characterization of the bleeding during endoscopy is key for endoscopic therapy. This study aimed to assess whether a deep learning model can aid in the classification of bleeding peptic ulcer disease. Methods Endoscopic still images of patients ( n = 1694) with peptic ulcer bleeding for the last 5 years were retrieved and reviewed. Overall, 2289 images were collected for deep learning model training, and 449 images were validated for the performance test. Two expert endoscopists classified the images into different classes based on their appearance. Four deep learning models, including Mobile Net V2, VGG16, Inception V4, and ResNet50, were proposed and pre-trained by ImageNet with the established convolutional neural network algorithm. A comparison of the endoscopists and trained deep learning model was performed to evaluate the model’s performance on a dataset of 449 testing images. Results The results first presented the performance comparisons of four deep learning models. The Mobile Net V2 presented the optimal performance of the proposal models. The Mobile Net V2 was chosen for further comparing the performance with the diagnostic results obtained by one senior and one novice endoscopists. The sensitivity and specificity were acceptable for the prediction of “normal” lesions in both 3-class and 4-class classifications. For the 3-class category, the sensitivity and specificity were 94.83% and 92.36%, respectively. For the 4-class category, the sensitivity and specificity were 95.40% and 92.70%, respectively. The interobserver agreement of the testing dataset of the model was moderate to substantial with the senior endoscopist. The accuracy of the determination of endoscopic therapy required and high-risk endoscopic therapy of the deep learning model was higher than that of the novice endoscopist. Conclusions In this study, the deep learning model performed better than inexperienced endoscopists. Further improvement of the model may aid in clinical decision-making during clinical practice, especially for trainee endoscopist.

Gas-phase isopropanol degradation by nonthermal plasma combined with Mn-Cu/-Al2O3 - Ken-Lin Chang; Yu-Chieh Lin; Ming-Ze Qiu; Chun-Wei Tu; Chih-Ping Chang; Jhong-Lin Wu; Yung-Chang Lin; Chien-Kuei Chang (Environmental Science and Pollution Research, 2021)

Correction to: Genomic Action of Sigma-1 Receptor Chaperone Relates to Neuropathic Pain - Shao-Ming Wang; Nino Goguadze; Yuriko Kimura; Yuko Yasui; Bin Pan; Tzu-Yun Wang; Yoki Nakamura; Yu-Ting Lin; Quinn H. Hogan; Katherine L. Wilson; Tsung-Ping Su; Hsiang-en Wu (Molecular Neurobiology, 2021)
A correction to this paper has been published: 10.1007/s12035-021-02310-3

Genomic Action of Sigma-1 Receptor Chaperone Relates to Neuropathic Pain - Shao-Ming Wang; Nino Goguadze; Yuriko Kimura; Yuko Yasui; Bin Pan; Tzu-Yun Wang; Yoki Nakamura; Yu-Ting Lin; Quinn H. Hogan; Katherine L. Wilson; Tsung-Ping Su; Hsiang-en Wu (Molecular Neurobiology, 2021)
Sigma-1 receptors (Sig-1Rs) are endoplasmic reticulum (ER) chaperones implicated in neuropathic pain. Here we examine if the Sig-1R may relate to neuropathic pain at the level of dorsal root ganglia (DRG). We focus on the neuronal excitability of DRG in a “spare nerve injury” (SNI) model of neuropathic pain in rats and find that Sig-1Rs likely contribute to the genesis of DRG neuronal excitability by decreasing the protein level of voltage-gated Cav2.2 as a translational inhibitor of mRNA. Specifically, during SNI, Sig-1Rs translocate from ER to the nuclear envelope via a trafficking protein Sec61β. At the nucleus, the Sig-1R interacts with cFos and binds to the promoter of 4E-BP1, leading to an upregulation of 4E-BP1 that binds and prevents eIF4E from initiating the mRNA translation for Cav2.2. Interestingly, in Sig-1R knockout HEK cells, Cav2.2 is upregulated. In accordance with those findings, we find that intra-DRG injection of Sig-1R agonist (+)pentazocine increases frequency of action potentials via regulation of voltage-gated Ca2+ channels. Conversely, intra-DRG injection of Sig-1R antagonist BD1047 attenuates neuropathic pain. Hence, we discover that the Sig-1R chaperone causes neuropathic pain indirectly as a translational inhibitor.

A dye combination for the staining of pollen coat and pollen wall - Xin-Lei Jia; Jing-Shi Xue; Fang Zhang; Chi Yao; Shi-Yi Shen; Chang-Xu Sui; Yu-Jia Peng; Qin-Lin Xu; Yi-Feng Feng; Wen-Jing Hu; Ping Xu; Zhong-Nan Yang (Plant Reproduction, 2021)

Cytotoxic p -terphenyls from the deep-sea-derived Aspergillus candidus - Yu-Kun Lin; Chun-Lan Xie; Cui-Ping Xing; Bao-Qu Wang; Xiao-Xue Tian; Jin-Mei Xia; Ling-Yun Jia; Ying-Ni Pan; Xian-Wen Yang (Natural Product Research, 2021)

Cytotoxic meroterpenoids from the marine sponge Dactylospongia elegans - Hao-Bing Yu; Zi-Fei Yin; Bin-Bin Gu; Jian-Peng Zhang; Shu-Ping Wang; Fan Yang; Hou-Wen Lin (Natural Product Research, 2021)

Study on Microwave Heating Order and Electromagnetic Characteristics of Copper and Gold Ores - Feng Lin; Xia-Ting Feng; Gao-Ming Lu; Xiang-Xin Su; Shi-Ping Li; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2021)

Exposed to Mercury-Induced Oxidative Stress, Changes of Intestinal Microflora, and Association between them in Mice - Yulan Zhao; Changming Zhou; Xiaoquan Guo; Guoliang Hu; Guyue Li; Yu Zhuang; Huabin Cao; Lin Li; Chonghong Xing; Caiying Zhang; Fan Yang; Ping Liu (Biological Trace Element Research, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Human β-Defensin 118 Attenuates Escherichia coli K88–Induced Inflammation and Intestinal Injury in Mice - Qian Lin; Qingqing Fu; Xiang Li; Yuheng Luo; Junqiu Luo; Daiwen Chen; Xiangbing Mao; Bing Yu; Ping Zheng; Zhiqing Huang; Jie Yu; Hui Yan; et al. (Probiotics and Antimicrobial Proteins, 2021)

Re-use of wasted sludge to treat industrial pollutants - Ru Wang; Li-ping Yu; Bibi Saima Zeb; Lin-jie Yuan; Meng-yu Liu; Lin-jiang Yuan (Water, Air, & Soil Pollution, 2021)

Biopharmaceutics Applications of Physiologically Based Pharmacokinetic Absorption Modeling and Simulation in Regulatory Submissions to the U.S. Food and Drug Administration for New Drugs - Fang Wu; Heta Shah; Min Li; Peng Duan; Ping Zhao; Sandra Suarez; Kimberly Raines; Yang Zhao; Meng Wang; Ho-pi Lin; John Duan; Lawrence Yu; et al. (The AAPS Journal, 2021)

Warming Iron-Limited Oceans Enhance Nitrogen Fixation and Drive Biogeographic Specialization of the Globally Important Cyanobacterium Crocosphaera - Nina Yang; Carlin A. Merkel; Yu-An Lin; Naomi M. Levine; Nicholas J. Hawco; Hai-Bo Jiang; Ping-Ping Qu; Michelle A. DeMers; Eric A. Webb; Fei-Xue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
Primary productivity in the nutrient-poor subtropical ocean gyres depends on new nitrogen inputs from nitrogen fixers that convert inert dinitrogen gas into bioavailable forms. Temperature and iron (Fe) availability constrain marine nitrogen fixation, and both are changing due to anthropogenic ocean warming. We examined the physiological responses of the globally important marine nitrogen fixer, Crocosphaera watsonii across its full thermal range as a function of iron availability. At the lower end of its thermal range, from 22 to 27°C, Crocosphaera growth, nitrogen fixation, and Nitrogen-specific Iron Use Efficiencies (N-IUEs, mol N fixed hour –1 mol Fe –1 ) increased with temperature. At an optimal growth temperature of 27°C, N-IUEs were 66% higher under iron-limited conditions than iron-replete conditions, indicating that low-iron availability increases metabolic efficiency. However, Crocosphaera growth and function decrease from 27 to 32°C, temperatures that are predicted for an increasing fraction of tropical oceans in the future. Altogether, this suggests that Crocosphaera are well adapted to iron-limited, warm waters, within prescribed limits. A model incorporating these results under the IPCC RCP 8.5 warming scenario predicts that Crocosphaera N-IUEs could increase by a net 47% by 2100, particularly in higher-latitude waters. These results contrast with published responses of another dominant nitrogen fixer ( Trichodesmium ), with predicted N-IUEs that increase most in low-latitude, tropical waters. These models project that differing responses of Crocosphaera and Trichodesmium N-IUEs to future warming of iron-limited oceans could enhance their current contributions to global marine nitrogen fixation with rates increasing by ∼91 and ∼22%, respectively, thereby shifting their relative importance to marine new production and also intensifying their regional divergence. Thus, interactive temperature and iron effects may profoundly transform existing paradigms of nitrogen biogeochemistry and primary productivity in open ocean regimes.

The adaptability of typical precipitation ensemble prediction systems in the Huaihe River basin, China - Han Wang; Ping-an Zhong; Fei-lin Zhu; Qing-wen Lu; Yu-fei Ma; Sun-yu Xu (Stochastic Environmental Research and Risk Assessment, 2021)

Dapagliflozin suppresses ER stress and protects doxorubicin-induced cardiotoxicity in breast cancer patients - Wei-Ting Chang; Yu-Wen Lin; Chung-Han Ho; Zhih-Cherng Chen; Ping-Yen Liu; Jhih-Yuan Shih (Archives of Toxicology, 2021)

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

Culturally Tailored Intervention to Promote Mammography Screening Practice Among Chinese American Women: a Systematic Review - Xuehui Zhang; Ping Li; Pingping Guo; Jie Wang; Na Liu; Shu Yang; Lin Yu; Xiumin Zhang; Wei Zhang (Journal of Cancer Education, 2020)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Erratum to: An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Intrusion of Kuroshio Helps to Diminish Coastal Hypoxia in the Coast of Northern South China Sea - Hon-Kit Lui; Chen-Tung Arthur Chen; Wei-Ping Hou; Jian-Ming Liau; Wen-Chen Chou; You-Lin Wang; Chau-Ron Wu; Jay Lee; Yi-Chia Hsin; Yan-Yu Choi (Frontiers in Marine Science, 2020)

Impact of prophylactic/preemptive donor lymphocyte infusion and intensified conditioning for relapsed/refractory leukemia: a real-world study - Yu Wang; Qi-Fa Liu; De-Pei Wu; Jing-Bo Wang; Xi Zhang; Heng-Xiang Wang; Feng Gao; Shun-Qing Wang; Zi-Min Sun; Jian Ouyang; Kai-Lin Xu; Su-Jun Gao; et al. (Science China Life Sciences, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

2D slope stability analysis based on Pan’s maximum principle - Xiao Gang Wang; Xing Chao Lin; Ping Sun; Xu Li; Yu Jie Wang; Yong Yu Ling (Bulletin of Engineering Geology and the Environment, 2020)

Colletotrichum neorubicola sp. nov., a new leaf anthracnose pathogen of raspberry from northeast China - Li-Ping Liu; Yu Wang; Peng-Lei Qiu; Bo Zhang; Lin Zhang; Na Wang; Yu Li; Jie Gao; Tom Hsiang (Mycological Progress, 2020)

An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Effect of Freezing and Thawing on Microstructure Damage and Dynamic Flexural Tension of Granite - Chuanju Liu; JunRen Deng; Songtao Yu; Ping Li; Yun Lin (Rock Mechanics and Rock Engineering, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Ecological risk assessment of species impacted by fisheries in waters off eastern Taiwan - Chih‐Yu Lin; Sheng‐Ping Wang; Wei‐Chuan Chiang; Shane Griffiths; Hsin‐Ming Yeh (Fisheries Management and Ecology, 2020)
An ecological risk assessment was undertaken using productivity‐susceptibility analysis (PSA) to determine the relative vulnerability of 52 species caught by fisheries in the waters off eastern Taiwan. Overall, eight and 20 species were classified as having high and moderate vulnerability, respectively, and the remaining 24 species were classified as having low vulnerability. The species with the highest vulnerability scores were caught mainly by longline and gillnet fisheries, highlighting the need for improved data collection to facilitate a more detailed investigation using more quantitative methods. The data quality analysis indicated that the quality of data was classified as “moderate” for economically important species. However, many species were considered data‐limited and thus collecting high‐resolution catch and effort information and conducting biological studies, especially relating to age, growth and reproduction, are recommended to improve the reliability of outputs from data‐limited assessments such as PSA.

Instantaneous phase inversion based on an unwrapping algorithm - Yu-Zhao Lin; Zhen-Chun Li; Kai Zhang; Ren-Wei Ding; Ping Jiang (Applied Geophysics, 2020)

A remote sensing monitoring method for alpine grasslands desertification in the eastern Qinghai-Tibetan Plateau - Qian Kuang; Quan-zhi Yuan; Ji-chong Han; Rong Leng; Yu-shuang Wang; Ke-hong Zhu; Shuo Lin; Ping Ren (Journal of Mountain Science, 2020)

Biological Protective Effects Against Vibrio Infections in Grouper Larvae Using the Strombidium sp. NTOU1, a Marine Ciliate Amenable for Scaled-Up Culture and With an Excellent Bacteriovorous Ability - Hung-Yun Lin; Wei-Yu Yeh; Sheng-Fang Tsai; Kuo-Ping Chiang; John Han-You Lin; Che-Chia Tsao; Han-Jia Lin (Frontiers in Marine Science, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Prior Antiplatelet Therapy, Excluding Phosphodiesterase Inhibitor Is Associated with Poor Outcome in Patients with Spontaneous Intracerebral Haemorrhage - Zhuo-Hao Liu; Chi-Hung Liu; Po-Hsun Tu; Ping K. Yip; Ching-Chang Chen; Yu-Chi Wang; Nan-Yu Chen; Yu-Sheng Lin (Translational Stroke Research, 2020)

A stochastic multi-objective optimization decision model for energy facility allocation: a case of liquefied petroleum gas station - Ming-Der Yang; Yi-Ping Chen; Chien-Tsung Wang; Ming-Jay Deng; Yu-Hao Lin; Ho-Wen Chen (Clean Technologies and Environmental Policy, 2020)

Instantaneous phase inversion based on an unwrapping algorithm - Yu-Zhao Lin; Zhen-Chun Li; Kai Zhang; Ren-Wei Ding; Ping Jiang (Applied Geophysics, 2020)

Stilbenoids from aerial parts of Dendrobium plicatile - Dan-Na Chen; Yu-Ye Wang; Wen-Jian Liu; Yue-Juan Chen; Ya-Ping Wu; Jing-Xian Wang; Feng He; Lin Jiang (Natural Product Research, 2020)

Therapeutic Efficacy of Subcutaneous and Intraperitoneal Injections of a Single Dose of Human Umbilical Mesenchymal Stem Cells in Acute and Chronic Colitis in a Mouse Model - Yu-Lung Chang; Huei-Yu Lo; Shun-Ping Cheng; Kuo-Ting Chang; Xiu-Fang Lin; Sheng-Ping Lee; Jason Ma; Ming-Ling Kuo; Ming-Fa Hsieh; Chin-Kan Chan (Journal of Medical and Biological Engineering, 2020)

Soil microbial activity and community composition as influenced by application of pig biogas slurry in paddy field in southeast China - Zhaoming Chen; Qiang Wang; Junwei Ma; Stephen Chapman; Ping Zou; Jing Ye; Qiaogang Yu; Wanchun Sun; Hui Lin; Lina Jiang (Paddy and Water Environment, 2020)

Mechanistic examination of methimazole-induced hepatotoxicity in patients with Grave’s disease: a metabolomic approach - Xuesong Li; Jialin Yang; Shasha Jin; Yu Dai; Yujuan Fan; Xiaofang Fan; Zhigang Li; Jianhua Yang; Wai-Ping Yau; Haishu Lin; Weimin Cai; Xiaoqiang Xiang (Archives of Toxicology, 2020)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Netrin-1 promotes the collective cell migration of liver cancer cells in a 3D cell culture model - Ping Han; Jingmei Liu; Yu Lei; Zhuoying Lin; Dean Tian; Wei Yan (Journal of Physiology and Biochemistry, 2019)

Comparative health risk of inhaled exposure to organic solvents, toxic metals, and hexavalent chromium from the use of spray paints in Taiwan - Chia-Hua Lin; Chia-Hsiang Lai; Yen-Ping Peng; Pei-Chun Wu; Kuen-Yuan Chuang; Ting-Yu Yen; Yao-Kai Xiang (Environmental Science and Pollution Research, 2019)

Paraventricular Thalamus as A Major Thalamic Structure for Wake Control - Yu-Feng Shao; Jian-Sheng Lin; Yi-Ping Hou (Neuroscience Bulletin, 2019)

Evaluation of Coherence Between ECG and PPG Derived Parameters on Heart Rate Variability and Respiration in Healthy Volunteers With/Without Controlled Breathing - Hao-Yu Jan; Mei-Fen Chen; Tieh-Cheng Fu; Wen-Chen Lin; Cheng-Lun Tsai; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2019)

Complete Genome Sequence of Pseudomonas Parafulva PRS09-11288, a Biocontrol Strain Produces the Antibiotic Phenazine-1-carboxylic Acid - Yu Zhang; Ping Chen; Guoyou Ye; Haiyan Lin; Deyong Ren; Longbiao Guo; Bo Zhu; Zhongwei Wang (Current Microbiology, 2019)

Leaf area–length allometry and its implications in leaf shape evolution - Peijian Shi; Mengdi Liu; David A. Ratkowsky; Johan Gielis; Jialu Su; Xiaojing Yu; Ping Wang; Lifang Zhang; Zhiyi Lin; Julian Schrader (Trees, 2019)

Interpreting air temperature generated from urban climatic map by urban morphology in Taipei - Yu-Cheng Chen; Tzu-Wen Lo; Wan-Yu Shih; Tzu-Ping Lin (Theoretical and Applied Climatology, 2019)

Comparative Transcriptome Analysis Reveals Differentially Expressed Genes and Signaling Pathways Between Male and Female Red-Tail Catfish (Mystus wyckioides) - Jun-Jie Wu; Yu-Lin Zhou; Zhong-Wei Wang; Guang-Hua Li; Fang-Peng Jin; Li-Li Cui; Hai-Tao Gao; Xin-Ping Li; Li Zhou; Jian-Fang Gui (Marine Biotechnology, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

Effect of different ethanolic concentrations on antioxidant properties and cytoprotective activities of Platostoma palustre Blume - Kuan-Hung Lin; Ming-Chih Shih; Po Wang; Yi-Ping Yu; Chun-Ping Lu (Natural Product Research, 2018)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

Interhemispheric functional connectivity for Alzheimer’s disease and amnestic mild cognitive impairment based on the triple network model - Zheng-luan Liao; Yun-fei Tan; Ya-ju Qiu; Jun-peng Zhu; Yan Chen; Si-si Lin; Ming-hao Wu; Yan-ping Mao; Jiao-jiao Hu; Zhong-xiang Ding; En-yan Yu (Journal of Zhejiang University-SCIENCE B, 2018)

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

NTF3 Is a Novel Target Gene of the Transcription Factor POU3F2 and Is Required for Neuronal Differentiation - Yi-Mei J. Lin; I-Lun Hsin; H. Sunny Sun; Shankung Lin; Yen-Ling Lai; Hsuan-Ying Chen; Ting-Yu Chen; Ya-Ping Chen; Yi-Ting Shen; Hung-Ming Wu (Molecular Neurobiology, 2018)

Detection, sequence analysis, and antibody prevalence of porcine deltacoronavirus in Taiwan - Tien-Huan Hsu; Hao-Ping Liu; Chieh-Yu Chin; Chinling Wang; Wan-Zhen Zhu; Bing-Lin Wu; Yu-Chung Chang (Archives of Virology, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Species composition, functional and phylogenetic distances correlate with success of invasive Chromolaena odorata in an experimental test - Yu‐Long Zheng; Jean H. Burns; Zhi‐Yong Liao; Yang‐ping Li; Jie Yang; Ya‐jun Chen; Jiao‐lin Zhang; Yu‐guo Zheng (Ecology Letters, 2018)
Biotic resistance may influence invasion success; however, the relative roles of species richness, functional or phylogenetic distance in predicting invasion success are not fully understood. We used biomass fraction of Chromolaena odorata , an invasive species in tropical and subtropical areas, as a measure of ‘invasion success’ in a series of artificial communities varying in species richness. Communities were constructed using species from Mexico (native range) or China (non‐native range). We found strong evidence of biotic resistance: species richness and community biomass were negatively related with invasion success; invader biomass was greater in plant communities from China than from Mexico. Harvesting time had a greater effect on invasion success in plant communities from China than on those from Mexico. Functional and phylogenetic distances both correlated with invasion success and more functionally distant communities were more easily invaded. The effects of plant‐soil fungi and plant allelochemical interactions on invasion success were species‐specific.

Phylogenetic analysis of IRIS L. from China on chloroplast TRNL-F sequences - Yu-Lin Jiang; Zhuo Huang; Jin-Qiu Liao; Hui-Xing Song; Xiao-Mei Luo; Su-Ping Gao; Ting Lei; Ming-Yan Jiang; Yin Jia; Qi-Bing Chen; Xiao-Fang Yu; Yong-Hong Zhou (Biologia, 2018)

A new pair of enantiomeric lignans from the fruits of Morinda citrifolia and their absolute configuration - Wen-Jian Liu; Yue-Juan Chen; Dan-Na Chen; Ya-Ping Wu; Yu-Jie Gao; Jing Li; Wen-Jun Zhong; Lin Jiang (Natural Product Research, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Temporal Profile and Severity Correlation of a Panel of Rat Spinal Cord Injury Protein Biomarkers - Zhihui Yang; Helen M. Bramlett; Ahmed Moghieb; Dongnan Yu; Ping Wang; Fan Lin; Carl Bauer; Tyler M. Selig; Emily Jaalouk; Amanda S. Weissman; Disa S. Rathore; Pammela Romo; et al. (Molecular Neurobiology, 2018)

Hsp90 regulation affects the treatment of glucocorticoid for pancreatitis-induced lung injury - Yan Zhao; Ren-Ping Xiong; Xing Chen; Ping Li; Ya-Lei Ning; Nan Yang; Yan Peng; Yu-Lin Jiang; Yuan-Guo Zhou (Molecular and Cellular Biochemistry, 2018)

A novel Fe(II)-Ca synergistic phosphorus removal process: process optimization and phosphorus recovery - Lin Qiu; Meng Zhang; Xiaoqing Yu; Ping Zheng (Environmental Science and Pollution Research, 2018)

Establishing a Forecast Mathematical Model of Sugarcane Yield and Brix Reduction Based on the Extent of Pokkah Boeng Disease - Ze-ping Wang; Lu Liu; Yu-chi Deng; Yi-jie Li; Ge-min Zhang; Shan-hai Lin; Tie-guang He (Sugar Tech, 2017)

Global changes of 5-hydroxymethylcytosine and 5-methylcytosine from normal to tumor tissues are associated with carcinogenesis and prognosis in colorectal cancer - Yi-ping Tian; Ai-fen Lin; Mei-fu Gan; Hao Wang; Dan Yu; Chong Lai; Dan-dan Zhang; Yi-min Zhu; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2017)

Overexpression of Arabidopsis ICR1 gene affects vegetative growth and anthesis - Da-Hui Li; Man-Li Li; Xiao-Bo Yu; Di Wu; Huan Xi; Yi Lin; Yong-Ping Cai (Biologia, 2017)

Punicalagin protects bovine endometrial epithelial cells against lipopolysaccharide-induced inflammatory injury - An Lyu; Jia-jia Chen; Hui-chuan Wang; Xiao-hong Yu; Zhi-cong Zhang; Ping Gong; Lin-shu Jiang; Feng-hua Liu (Journal of Zhejiang University-SCIENCE B, 2017)

A simple approach for the development of urban climatic maps based on the urban characteristics in Tainan, Taiwan - Yu-Cheng Chen; Tzu-Ping Lin; Chien-Ting Lin (International Journal of Biometeorology, 2017)

Extraction and Characterization of Pepsin Soluble Collagen from the Body Wall of Sea Cucumber Acaudina leucoprocta - Saijun Lin; Ya-Ping Xue; Enli San; Tan Chee Keong; Lifang Chen; Yu-Guo Zheng (Journal of Aquatic Food Product Technology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

In vitro reprogramming of rat bmMSCs into pancreatic endocrine-like cells - Hong-Tu Li; Fang-Xu Jiang; Ping Shi; Tao Zhang; Xiao-Yu Liu; Xue-Wen Lin; Zhong-Yan San; Xi-Ning Pang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Erratum to: Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

One-step reverse transcription loop-mediated isothermal amplification for the detection of Capsicum chlorosis virus in Phalaenopsis orchids - Cheng-Ping Kuan; Yu-Fei Lin; Yu-Chun Lin; Chin-Chih Chen (Journal of General Plant Pathology, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2016)

Review on Saussurea laniceps, a potent medicinal plant known as “snow lotus”: botany, phytochemistry and bioactivities - Qi-Lei Chen; Xi-Yu Chen; Lin Zhu; Hu-Biao Chen; Hing-Man Ho; Wing-Ping Yeung; Zhong-Zhen Zhao; Tao Yi (Phytochemistry Reviews, 2016)

A new tigliane-type diterpene from Euphorbia dracunculoides Lam - Lin-Feng Dai; Qian Liang; Tie Liu; Ming-Yu He; Ping Zhao; Wen-Hui Xu (Natural Product Research, 2016)

Comparison of ultrastructural and physiological changes of potato (Solanum tuberosum L.) plantlets subjected to salt and modeling drought stresses - Jiang-Ping Bai; Hui-Juan Gao; Hong-Yu Yang; Yan Lou; Jun-Lian Zhang; Di Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2016)

A new phenylethanoid glycoside from Orobanche cernua Loefling - Zheng-yi Qu; Yu-wei Zhang; Si-wen Zheng; Chun-lin Yao; Yin-ping Jin; Pei-he Zheng; Cheng-he Sun; Ying-ping Wang (Natural Product Research, 2016)

Spatial and Age-Dependent Hair Cell Generation in the Postnatal Mammalian Utricle - Zhen Gao; Michael C. Kelly; Dehong Yu; Hao Wu; Xi Lin; Fang-lu Chi; Ping Chen (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Canonical and non-canonical Wnt signaling control the regeneration of amputated rodent vibrissae follicles - Yan-Ping Yuan; Keng Huang; Yan-Min Xu; Xian-Cai Chen; Hai-Hong Li; Bo-Zhi Cai; Yang Liu; Huan Zhang; Yu Li; Chang-Min Lin (Journal of Molecular Histology, 2016)

A new method for estimating effect size distribution and heritability from genome-wide association summary results - Lei Zhang; Yue-Ping Shen; Wen-Zhu Hu; Shu Ran; Yong Lin; Shu-Feng Lei; Yong-Hong Zhang; Christopher J. Papasian; Nengjun Yi; Yu-Fang Pei (Human Genetics, 2016)

Effect of resin content and substrate on the emission of BTEX and carbonyls from low-VOC water-based wall paint - Ping Zhao; Yu-Hsiang Cheng; Chi-Chi Lin; Yu-Lin Cheng (Environmental Science and Pollution Research, 2016)

Multiobjective Optimal Design of Sewerage Rehabilitation by Using the Nondominated Sorting Genetic Algorithm-II - Yu-Hao Lin; Yi-Ping Chen; Ming-Der Yang; Tung-Ching Su (Water Resources Management, 2016)

Erratum to: The collective nuclear migration of p53 and phosphorylated S473 of Akt during ellipticine-mediated apoptosis in human lung epithelial cancer cells - Jing-Ping Wang; Ya-Chu Yu; Shih-Ping Chen; Huan-Chang Liang; Chia-Wei Lin; Kang Fang (Molecular and Cellular Biochemistry, 2015)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

The collective nuclear migration of p53 and phosphorylated S473 of Akt during ellipticine-mediated apoptosis in human lung epithelial cancer cells - Jing-Ping Wang; Ya-Chu Yu; Shih-Ping Chen; Huan-Chang Liang; Chia-Wei Lin; Kang Fang (Molecular and Cellular Biochemistry, 2015)

Characterization of important odorants in four steamed Coilia ectenes from China by gas chromatography–mass spectrometry–olfactometry - Lin-min Zhao; Wei Wu; Ning-ping Tao; Yu-qi Li; Na Wu; Xiao Qin (Fisheries Science, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

IL-1β Induces MMP-9-Dependent Brain Astrocytic Migration via Transactivation of PDGF Receptor/NADPH Oxidase 2-Derived Reactive Oxygen Species Signals - Chuen-Mao Yang; Hsi-Lung Hsieh; Ping-Hsien Yu; Chih-Chung Lin; Shiau-Wen Liu (Molecular Neurobiology, 2015)

Soil organic matter fractions under different vegetation types in permafrost regions along the Qinghai-Tibet Highway, north of Kunlun Mountains, China - Wen Shang; Lin Zhao; Xiao-dong Wu; Yu-qiang Li; Guang-yang Yue; Yong-hua Zhao; Yong-ping Qiao (Journal of Mountain Science, 2015)

Expression of Wnt/β-catenin signaling, stem-cell markers and proliferating cell markers in rat whisker hair follicles - Chang-min Lin; Yan-ping Yuan; Xian-cai Chen; Hai-hong Li; Bo-zhi Cai; Yang Liu; Huan Zhang; Yu Li; Keng Huang (Journal of Molecular Histology, 2015)

Nucleotide composition bias and codon usage trends of gene populations in Mycoplasma capricolum subsp. capricolum and M. agalactiae - XIAO-XIA MA; YU-PING FENG; JIA-LING BAI; DE-RONG ZHANG; XIN-SHI LIN; ZHONG-REN MA (Journal of Genetics, 2015)

A Novel Oral Preparation of Hydroxysafflor Yellow A Base on a Chitosan Complex: A Strategy to Enhance the Oral Bioavailability - Guan-nan Ma; Fang-lin Yu; Shan Wang; Zhi-ping Li; Xiang-yang Xie; Xing-guo Mei (AAPS PharmSciTech, 2015)

Fast-growing and poorly shade-tolerant invasive species may exhibit higher physiological but not morphological plasticity compared with non-invasive species - Yu-Ping Hou; Shao-Lin Peng; Zhen-Guang Lin; Qiao-Qiao Huang; Guang-Yan Ni; Na Zhao (Biological Invasions, 2015)

Transcriptional regulation of the iac locus from Acinetobacter baumannii by the phytohormone indole-3-acetic acid - Hung-Yu Shu; Ling-Chun Lin; Tze-Kang Lin; Hao-Ping Chen; Hsueh-Hui Yang; Kou-Cheng Peng; Guang-Huey Lin (Antonie van Leeuwenhoek, 2015)

Association between the CYP1A2 polymorphisms and risk of cancer: a meta-analysis - Wen-Xia Sun; Ying-Hua Chen; Zhi-Zhong Liu; Jian-Jun Xie; Wei Wang; Ya-Ping Du; Yu Chen; Xu-Liang Shen; Xiao-Feng He; Li-Xia Wu; Wu Wei; Lin Zhang (Molecular Genetics and Genomics, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Increase of Zinc Finger Protein 179 in Response to CCAAT/Enhancer Binding Protein Delta Conferring an Antiapoptotic Effect in Astrocytes of Alzheimer’s Disease - Shao-Ming Wang; Yi-Chao Lee; Chiung-Yuan Ko; Ming-Derg Lai; Ding-Yen Lin; Ping-Chieh Pao; Jhih-Ying Chi; Yu-Wei Hsiao; Tsung-Lin Liu; Ju-Ming Wang (Molecular Neurobiology, 2015)

Characteristics of Dew Formation and Distribution, and Its Contribution to the Surface Water Budget in a Semi-arid Region in China - Qiang Zhang; Sheng Wang; Fu-Lin Yang; Ping Yue; Tong Yao; Wen-Yu Wang (Boundary-Layer Meteorology, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

Effects of combined application of organic and inorganic fertilizers plus nitrification inhibitor DMPP on nitrogen runoff loss in vegetable soils - Qiaogang Yu; Junwei Ma; Ping Zou; Hui Lin; Wanchun Sun; Jianzhen Yin; Jianrong Fu (Environmental Science and Pollution Research, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Association of IL-18 promoter gene polymorphisms with rheumatoid arthritis: a meta-analysis - Li-Ping Cai; Li-Juan Zhou; Shun-Yu Lu; Ying-E Liang; Xiao-Ying Chen; Lin Liu; Jun Lin (Molecular Biology Reports, 2014)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Observation of the middle intestinal tight junction structure, cloning and studying tissue distribution of the four Claudin genes of the grass carp (Ctenopharyngodon idellus) - Fan Xu; Yuan-Tu Ye; Chun-Fang Cai; Ping Wu; Lin Song; Meng Liu; Lin-Jie Yao; Jiao-Jiao Dong; Yu-Wei Huang; Zhi Gong; Jie Qin; Liang Song (Fish Physiology and Biochemistry, 2014)

Expression screening and annotation of Sepiella maindroni ink sac cDNA library - WEI-WEI SONG; CHANG-KAO MU; SHAO CHU; YU-YU ZHANG; PING-PING ZHAN; CHUN-LIN WANG (Journal of Genetics, 2014)

Development, characterization and cross-species amplification of new microsatellite primers from an endemic species Cinnamomum kanehirae (Lauraceae) in Taiwan - Kuo-Hsiang Hung; Chia-Hung Lin; Huei-Chuan Shih; Yu-Chung Chiang; Li-Ping Ju (Conservation Genetics Resources, 2014)

The role of Mss11 in Candida albicans biofilm formation - Pei-Wen Tsai; Yu-Ting Chen; Cheng-Yao Yang; Hsueh-Fen Chen; Te-Sheng Tan; Tzung-Wei Lin; Wen-Ping Hsieh; Chung-Yu Lan (Molecular Genetics and Genomics, 2014)

SLDP: a Novel Protein Related to Caleosin Is Associated with the Endosymbiotic Symbiodinium Lipid Droplets from Euphyllia glabrescens - Buntora Pasaribu; I-Ping Lin; Jason T. C. Tzen; Guang-Yuh Jauh; Tung-Yung Fan; Yu-Min Ju; Jing-O Cheng; Chii-Shiarng Chen; Pei-Luen Jiang (Marine Biotechnology, 2014)

Spatial distribution of soil erosion and suspended sediment transport rate for Chou-Shui river basin - Chin-Ping Lin; Ching-Nuo Chen; Yu-Min Wang; Chih-Heng Tsai; Chang-Tai Tsai (Journal of Earth System Science, 2014)

The Melanogenesis-Inhibitory Effect and the Percutaneous Formulation of Ginsenoside Rb1 - Lin Wang; Ai-Ping Lu; Zhi-Ling Yu; Ricky N. S. Wong; Zhao-Xiang Bian; Hoi-Hin Kwok; Patrick Ying-Kit Yue; Li-Min Zhou; HuBiao Chen; Min Xu; Zhijun Yang (AAPS PharmSciTech, 2014)

Indian Ocean variability in the CMIP5 multi-model ensemble: the zonal dipole mode - Lin Liu; Shang-Ping Xie; Xiao-Tong Zheng; Tim Li; Yan Du; Gang Huang; Wei-Dong Yu (Climate Dynamics, 2014)

A new epimer of ocotillol from stems and leaves of American ginseng - Liu Han; Mei-Yu Lin; Qian Zheng; Hai-Yu Liu; Hai-Yan Liu; Gang Dong; Jin-Ping Liu; Ping-Ya Li (Natural Product Research, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Inactivation kinetics of formaldehyde on N-acetyl-β-d-glucosaminidase from Nile tilapia (Oreochromis niloticus) - Wei-Ni Zhang; Ding-Ping Bai; Xin-Yu Lin; Qing-Xi Chen; Xiao-Hong Huang; Yi-Fan Huang (Fish Physiology and Biochemistry, 2014)

Nutrient limitation in Auxenochlorella protothecoides induces qualitative changes of fatty acid and expression of caleosin as a membrane protein associated with oil bodies - Buntora Pasaribu; I-Ping Lin; Chii-Shiarng Chen; Chi-Yu Lu; Pei-Luen Jiang (Biotechnology Letters, 2014)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Analysis of synonymous codon usage patterns in the genus Rhizobium - Xinxin Wang; Liang Wu; Ping Zhou; Shengfeng Zhu; Wei An; Yu Chen; Lin Zhao (World Journal of Microbiology and Biotechnology, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

The effects of the codon usage and translation speed on protein folding of 3Dpol of foot-and-mouth disease virus - Xiao-xia Ma; Yu-ping Feng; Jun-lin Liu; Bing Ma; Li Chen; Yong-qing Zhao; Peng-hui Guo; Jun-zhen Guo; Zhong-ren Ma; Jie Zhang (Veterinary Research Communications, 2013)

Effects of extracellular calcium on viability and osteogenic differentiation of bone marrow stromal cells in vitro - Shaowen Cheng; Wei Wang; Zhongqin Lin; Ping Zhou; Xiaolei Zhang; Wei Zhang; Qingyu Chen; Dongquan Kou; Xiaozhou Ying; Yue Shen; Xiaojie Cheng; Ziming Yu; et al. (Human Cell, 2013)

Computer Aided Alignment and Quantitative 4D Structural Plasticity Analysis of Neurons - Ping-Chang Lee; Hai-yan He; Chih-Yang Lin; Yu-Tai Ching; Hollis T. Cline (Neuroinformatics, 2013)

Renin–Angiotensin System Modulates Neurotransmitters in the Paraventricular Nucleus and Contributes to Angiotensin II-Induced Hypertensive Response - Jie Qi; Dong-Mei Zhang; Yu-Ping Suo; Xin-Ai Song; Xiao-Jing Yu; Carrie Elks; Yuan-Xi Lin; Yan-Yan Xu; Wei-Jin Zang; Zhiming Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

The active alkaloids of Gelsemium elegans Benth. are potent anxiolytics - Ming Liu; Hui-Hui Huang; Jian Yang; Yan-Ping Su; Hong-Wei Lin; Li-Qing Lin; Wei-Jian Liao; Chang-Xi Yu (Psychopharmacology, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

A molecular diagnosis method using real-time PCR for quantification and detection of Fusarium oxysporum f. sp. cubense race 4 - Ying-Hong Lin; Ching-Chung Su; Chih-Ping Chao; Chi-Yu Chen; Chung-Jan Chang; Jenn-Wen Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2013)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

High levels of glucose induce “metabolic memory” in cardiomyocyte via epigenetic histone H3 lysine 9 methylation - Xi-Yong Yu; Yong-Jian Geng; Jia-Liang Liang; Saidan Zhang; He-Ping Lei; Shi-Long Zhong; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yangxin Li (Molecular Biology Reports, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Highly efficient decolorization of Malachite Green by a novel Micrococcus sp. strain BD15 - Lin-Na Du; Ming Zhao; Gang Li; Xiao-Ping Zhao; Yu-Hua Zhao (Environmental Science and Pollution Research, 2012)

Ralstonia solanacearum nlpD (RSc1206) contributes to host adaptation - Chi-Yin Hsieh; Jaw-Fen Wang; Pei-Cheng Huang; Der-Kang Lu; Yu-Mei Lin; Wen-Chieh Yang; Chiu-Ping Cheng (European Journal of Plant Pathology, 2012)

An alternative method for cDNA cloning from surrogate eukaryotic cells transfected with the corresponding genomic DNA - Lin-yong Hu; Chen-chen Cui; Yu-jie Song; Xiang-guo Wang; Ya-ping Jin; Ai-hua Wang; Yong Zhang (Biotechnology Letters, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Cloning and the expression pattern of Spätzle gene during embryonic development and bacterial challenge in Artemia sinica - Lu-ping Zheng; Lin Hou; Miao Yu; Xiang Li; Xiang-yang Zou (Molecular Biology Reports, 2012)

Identification and characterization of an indigo-producing oxygenase involved in indole 3-acetic acid utilization by Acinetobacter baumannii - Guang-Huey Lin; Hao-Ping Chen; Jui-Hsin Huang; Tze-Tze Liu; Tze-Kang Lin; Shih-Jon Wang; Cheng-Hsing Tseng; Hung-Yu Shu (Antonie van Leeuwenhoek, 2012)

Immobilization of foreign protein into polyhedra of Bombyx mori nucleopolyhedrovirus (BmNPV) - Xing-wei Xiang; Rui Yang; Lin Chen; Xiao-long Hu; Shao-fang Yu; Cui-ping Cao; Xiao-feng Wu (Journal of Zhejiang University-SCIENCE B, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

ADAM17 regulates prostate cancer cell proliferation through mediating cell cycle progression by EGFR/PI3K/AKT pathway - Ping Lin; Xicai Sun; Tian Feng; Haifeng Zou; Ying Jiang; Zijun Liu; Dandan Zhao; Xiaoguang Yu (Molecular and Cellular Biochemistry, 2012)

Growth inhibition and apoptotic effect of alpha-eleostearic acid on human breast cancer cells - Tingting Zhang; Yanping Gao; Yu Mao; Quanbo Zhang; Caiyu Lin; Ping Lin; Jie Zhang; Xiujie Wang (Journal of Natural Medicines, 2012)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Levels and Congener Profiles of Particle-bound Polybrominated Dibenzo-p-dioxins/furans (PBDD/Fs) in Ambient Air around Guangzhou, China - Huiru Li; Lin Zhou; Ligui Mo; Ping’an Peng; Guoying Sheng; Jiamo Fu; Zhiqiang Yu (Bulletin of Environmental Contamination and Toxicology, 2011)

Aucubin modulates Bcl-2 family proteins expression and inhibits caspases cascade in H2O2-induced PC12 cells - Hong Yu Xue; Dong Yan Niu; Gui Zhen Gao; Qiu Ye Lin; Li Ji Jin; Yong Ping Xu (Molecular Biology Reports, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Novel Fluorescent Molecular Clips: Selective Recognition Towards Fe3+ in Aqueous Solution - Lin Li; Neng-fang She; Zhuan Fei; Pui-kin So; Yu-zhou Wang; Li-ping Cao; An-xin Wu; Zhong-ping Yao (Journal of Fluorescence, 2011)

Candida tropicalis: characterization of a strain capable of degrading high concentrations of phenol - Liming Wang; Yanwen Lin; Linyan Yang; Ping Yu; Zhixiong Xie; Yunbai Luo (Biotechnology Letters, 2011)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Single amino acid residue changes in subsite −1 of levansucrase from Zymomonas mobilis 10232 strongly influence the enzyme activities and products - Shuying Li; Yongliang Yan; Zhengfu Zhou; Haiying Yu; Yuhua Zhan; Wei Zhang; Ming Chen; Wei Lu; Shuzhen Ping; Min Lin (Molecular Biology Reports, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Do higher resource capture ability and utilization efficiency facilitate the successful invasion of native plants? - Xing-Yan Shen; Shao-Lin Peng; Bao-Ming Chen; Jun-Xiao Pang; Lei-Yi Chen; Hao-Ming Xu; Yu-Ping Hou (Biological Invasions, 2011)

Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2011)

Prevention of cerebral ischemia-induced memory deficits by inhibition of phosphodiesterase-4 in rats - Ling-Xia Li; Yu-Fang Cheng; Huan-Bing Lin; Chuang Wang; Jiang-Ping Xu; Han-Ting Zhang (Metabolic Brain Disease, 2011)

Risk assessment of inhalation exposure to polycyclic aromatic hydrocarbons in Taiwanese workers at night markets - Ping Zhao; Kuo-Pin Yu; Chi-Chi Lin (International Archives of Occupational and Environmental Health, 2011)

β-Actin is a downstream effector of the PI3K/AKT signaling pathway in myeloma cells - Yen-Peng Ho; Chi-Wei Kuo; Yuan-Tong Hsu; Yu-Shan Huang; Li-Ping Yew; Wei-Feng Huang; Kuo-Chih Lin; Jung-Hsin Hsu (Molecular and Cellular Biochemistry, 2011)

Phylogenetic position of a threatened stag beetle, Lucanus datunensis (Coleoptera: Lucanidae) in Taiwan and implications for conservation - Chung-Ping Lin; Jen-Pan Huang; Yat-Hung Lee; Ming-Yu Chen (Conservation Genetics, 2011)

Inhibition of an invasive plant (Mikania micrantha H.B.K.) by soils of three different forests in lower subtropical China - Yu-Ping Hou; Shao-Lin Peng; Bao-Ming Chen; Guang-Yan Ni (Biological Invasions, 2011)

Wake-promoting agent modafinil worsened attentional performance following REM sleep deprivation in a young-adult rat model of 5-choice serial reaction time task - Yia-Ping Liu; Che-Se Tung; Yu-Lung Lin; Chia-Hsin Chuang (Psychopharmacology, 2011)

Th17 promotes acute rejection following liver transplantation in rats - Xiao-jun Xie; Yu-fu Ye; Lin Zhou; Hai-yang Xie; Guo-ping Jiang; Xiao-wen Feng; Yong He; Qin-fen Xie; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Investigation of the association between all-trans-retinol dehydrogenase (RDH8) polymorphisms and high myopia in Chinese - Yan-shu Yu; Lin-ling Wang; Ye Shen; Maurice K. H. Yap; Shea-ping Yip; Wei Han (Journal of Zhejiang University-SCIENCE B, 2010)

Green Preference Enhances the Attractiveness of and Promotes Feeding on NaCl Resource in the Yellow-spined Bamboo Locust, Ceracris kiangsu - Hai-Ping Yu; Zhi-Tian Wang; Kai Xiao; Lin Shao; Guo-Qing Li (Journal of Insect Behavior, 2010)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Bacterial community of very wet and acidic subalpine forest and fire-induced grassland soils - Yu-Te Lin; Ching-Ping Lin; Shu-Miaw Chaw; William B. Whitman; David C. Coleman; Chih-Yu Chiu (Plant and Soil, 2010)

Heredity, diet and lifestyle as determining risk factors for the esophageal cancer on Nanao Island in Southern China - Min Liu; Min Su; Dong-Ping Tian; Guo-Hong Zhang; He-Lin Yang; Yu-Xia Gao (Familial Cancer, 2010)

Probing the catalytically essential residues of a recombinant dipeptidyl carboxypeptidase from Escherichia coli - Huei-Fen Lo; Hsiang-Ling Chen; Shao-Yu Yen; Ping-Lin Ong; Wen-Shiue Chang; Chen-Tien Chang (Biologia, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Protein kinase C regulates neurite outgrowth in spinal cord neurons - Ping Yang; Zhen-Qiang Li; Lin Song; Yu-Qin Yin (Neuroscience Bulletin, 2010)

Intratumoral as well as peritumoral lymphatic vessel invasion correlates with lymph node metastasis and unfavourable outcome in colorectal cancer - Mei Lin; Shu-Pei Ma; Hui-Zhong Lin; Ping Ji; Dan Xie; Jian-Xian Yu (Clinical & Experimental Metastasis, 2010)

Erratum to: Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Benzoate Catabolite Repression of the Phenol Degradation in Acinetobacter calcoaceticus PHEA-2 - Yuhua Zhan; Haiying Yu; Yongliang Yan; Shuzhen Ping; Wei Lu; Wei Zhang; Ming Chen; Min Lin (Current Microbiology, 2009)

Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Memory deficits and neurochemical changes induced by C-reactive protein in rats: implication in Alzheimer’s disease - Huan-Bing Lin; Xue-Mei Yang; Tie-Jun Li; Yu-Fang Cheng; Han-Ting Zhang; Jiang-Ping Xu (Psychopharmacology, 2009)

A ThCAP gene from Tamarix hispida confers cold tolerance in transgenic Populus (P. davidiana × P. bolleana) - Xiao-Hong Guo; Jing Jiang; Shi-Jie Lin; Bai-Chen Wang; Yu-Cheng Wang; Gui-Feng Liu; Chuan-Ping Yang (Biotechnology Letters, 2009)

Transcriptional analysis of the hsp70 gene in a haloarchaeon Natrinema sp. J7 under heat and cold stress - Hao Zhang; Peng Cui; Lu Lin; Ping Shen; Bing Tang; Yu-Ping Huang (Extremophiles, 2009)

KIFC1 participates in acrosomal biogenesis, with discussion of its importance for the perforatorium in the Chinese mitten crab Eriocheir sinensis - Keming Yu; Lin Hou; Jun-Quan Zhu; Xue-Ping Ying; Wan-Xi Yang (Cell and Tissue Research, 2009)

Deletion analysis of the C-terminal region of a molecular chaperone DnaK from Bacillus licheniformis - Wan-Chi Liang; Min-Guan Lin; Meng-Chun Chi; Hui-Yu Hu; Huei-Fen Lo; Hui-Ping Chang; Long-Liu Lin (Archives of Microbiology, 2009)

Analysis of the mechanisms underlying the endothelium-dependent antivasoconstriction of puerarin in rat aorta - Li-Ping Yan; Yu-Lan Zhuang; Shun-Wan Chan; Shi-Lin Chen; Gang-Gang Shi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Genes Involved in the Benzoate Catabolic Pathway in Acinetobacter calcoaceticus PHEA-2 - Yuhua Zhan; Haiying Yu; Yongliang Yan; Ming Chen; Wei Lu; Shuying Li; Zixin Peng; Wei Zhang; Shuzhen Ping; Jin Wang; Min Lin (Current Microbiology, 2008)

Eighteen novel polymorphic microsatellite loci developed from the Père David’s deer (Elaphurus davidianus) - Hai-Long Wu; Xiao-Wei Ni; Lin-Yuan Zhang; Jin-Shi Xia; Zhen-Yu Zhong; Guo-Ping Zhu; Qiu-Hong Wan (Conservation Genetics, 2008)

The Influence of Center of Rotation on the Assessment of Trabecular Bone Densitometric and Structural Properties - Zhi-Feng Sheng; Ru-Chun Dai; Xian-Ping Wu; Yu-Lin Ma; Kang Xu; Yu-Hai Zhang; Ye-Bin Jiang; Er-Yuan Liao (Annals of Biomedical Engineering, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Spatiotemporal distribution of arsineic species of oysters (Crassostrea gigas) in the coastal area of southwestern Taiwan - Chen-Wuing Liu; Yung-Kay Huang; Yu-Mei Hsueh; Kao-Hung Lin; Cheng-Shin Jang; Lan-Ping Huang (Environmental Monitoring and Assessment, 2008)

Ex vivo expansion and pluripotential differentiation of cryopreserved human bone marrow mesenchymal stem cells - Ying Xiang; Qiang Zheng; Bing-bing Jia; Guo-ping Huang; Yu-lin Xu; Jin-fu Wang; Zhi-jun Pan (Journal of Zhejiang University-SCIENCE B, 2007)

Avian Reovirus activates a novel proapoptotic signal by linking Src to p53 - Lin Ping-Yuan; Liu Hung-Jen; Lai Meng-Jiun; Yu Feng-Ling; Hsu Hsue-Yin; Lee Jeng-Woei; Shih Wen-Ling (Apoptosis, 2006)

IGFBP7 plays a potential tumor suppressor role against colorectal carcinogenesis with its expression associated with DNA hypomethylation of exon 1 - Wen-jing Ruan; Jie Lin; En-ping Xu; Fang-ying Xu; Yu Ma; Hong Deng; Qiong Huang; Bing-jian Lv; Hu Hu; Jing Cui; Mei-juan Di; Jian-kang Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2006)

Promoter trapping in Magnaporthe grisea - Xiao-hong Liu; Jian-ping Lu; Jiao-yu Wang; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2006)

Representative appressorium stage cDNA library of Magnaporthe grisea - Jian-ping Lu; Tong-bao Liu; Xiao-yun Yu; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2005)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Genetic Diversity and Relationship of Yunnan Native Cattle Breeds and Introduced Beef Cattle Breeds - Ying Yu; Lin-Sheng Lian; Ji-Kun Wen; Xian-Wei Shi; Fang-Xian Zhu; Long Nie; Ya-Ping Zhang (Biochemical Genetics, 2004)

Erratum: Cloning and sequencing of the phycocyanin gene from Spirulina maxima and its evolutionary analysis - Ping Yu; Jian-Rong Li; Pei-Lin Cen; Song Qin; Fan Lin (Journal of Applied Phycology, 2003)

Cloning and sequencing of the phycocyanin gene from Spirulina maxima and its evolutionary analysis - Ping Yu; Jian-Rong Li; Pei-Lin Cen (Journal of Applied Phycology, 2002)

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)

Long-term monitoring of the coral reef fish communities around a nuclear power plant - Rong-Quen Jan; Jeng-Ping Chen; Chun-Yu Lin; Kwang-Tsao Shao (Aquatic Ecology, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Localization of the genes encoding the type I diabetes autoantigens, protein-tyrosine phosphatases IA2 and IAR - Grant Morahan; Dexing Huang; Wei-Ping Yu; Lin Cui; Henry DeAizpurua; Catherine J. Pallen (Mammalian Genome, 1998)